A genomic strategy for precision medicine in rare diseases: integrating customized algorithms into clinical practice. - Méndez-Vidal, Cristina; Bravo-Gil, Nereida; Perez-Florido, Javier; Marcos-Luque, Irene; Fernández, Raquel M; Fernandez-Rueda, Jose Luis; González-del Pozo, María; Martín-Sánchez, Marta; Fernández-Suárez, Elena; Mena, Marcela; Carmona, Rosario; Dopazo, Joaquin; et al. (J Transl Med, 2025)
BACKGROUND: Despite the use of Next-Generation Sequencing (NGS) as the gold standard for the diagnosis of rare diseases, its clinical implementation has been challenging, limiting the cost-effectiveness of NGS and the understanding, control and safety essential for decision-making in clinical applications. Here, we describe a personalized NGS-based strategy integrating precision medicine into a public healthcare system and its implementation in the routine diagnosis process during a five-year pilot program. METHODS: Our approach involved customized probe designs, the generation of virtual panels and the development of a personalized medicine module (PMM) for variant prioritization. This strategy was applied to 6500 individuals including 6267 index patients and 233 NGS-based carrier screenings. RESULTS: Causative variants were identified in 2061 index patients (average 32.9%, ranging from 12 to 62% by condition). Also, 131 autosomal-recessive cases could be partially genetically diagnosed. These results led to over 5000 additional studies including carrier, prenatal and preimplantational tests or pharmacological and gene therapy treatments. CONCLUSION: This strategy has shown promising improvements in the diagnostic rate, facilitating timely diagnosis and gradually expanding our services portfolio for rare diseases. The steps taken towards the integration of clinical and genomic data are opening new possibilities for conducting both retrospective and prospective healthcare studies. Overall, this study represents a major milestone in the ongoing efforts to improve our understanding and clinical management of rare diseases, a crucial area of medical research and care.
Keywords: Algorithms; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Precision Medicine; rare diseases

Metatranscriptomic analysis reveals gut microbiome bacterial genes in pyruvate and amino acid metabolism associated with hyperuricemia and gout in humans. - Martínez-Nava, Gabriela Angélica; Altamirano-Molina, Efren; Vázquez-Mellado, Janitzia; Casimiro-Soriguer, Carlos S; Dopazo, Joaquin; Lozada-Pérez, Carlos; Herrera-López, Brígida; Martínez-Gómez, Laura Edith; Martínez-Armenta, Carlos; Guido-Gómora, Dafne Lissete; Valle-Gutiérrez, Sarahí; Suarez-Ahedo, Carlos; et al. (Sci Rep, 2025)
Several pathologies with metabolic origin, such as hyperuricemia and gout, have been associated with the gut microbiota taxonomic profile. However, there is no evidence of which bacterial genes are being expressed in the gut microbiome, and of their potential effects on hyperuricemia and gout. We sequenced the RNA of 26 fecal samples from 10 healthy normouricemic controls, 10 with asymptomatic hyperuricemia (AH), and six gout patients. The coding sequences were mapped to KEGG orthologues (KO). We compared the expression levels using generalized linear models and validated the expression of four KO in a larger sample by qRT-PCR. A distinct genetic expression pattern was identified among groups. AH individuals and gout patients showed an over-expression of KOs mainly related to pyruvate metabolism (Log2foldchange > 23, p-adj ≤ 3.56 × 10), the pentose pathway (Log2foldchange > 24, p-adj < 1.10 × 10) and purine metabolism (Log2foldchange > 22, p-adj < 1.25 × 10). AH subjects had lower expression of KO related to glycine metabolism (Log2foldchange=-18, p-adj < 1.72 × 10) than controls. Gout patients had lower expression (Log2foldchange=-22.42, p-adj < 3.31 × 10) of a KO involved in phenylalanine biosynthesis, in comparison to controls and AH subjects. The over-expression seen for the KO related to pyruvate metabolism and the pentose pathway in gout patients´ microbiome was validated. There is a differential gene expression pattern in the gut microbiome of normouricemic individuals, AH subjects and gout patients. These differences are mainly located in metabolic pathways involved in acetate precursors and bioavailability of amino acids.
Keywords: Adult; Aged; Amino Acids; Bacteria; Case-Control Studies; Feces; Female; Gastrointestinal Microbiome; Gene Expression Profiling; Genes, Bacterial; Gout; Humans; Hyperuricemia; Male; Middle Aged; Pyruvic Acid; Transcriptome

Characterization of the Common Genetic Variation in the Spanish Population of Navarre. - Maillo, Alberto; Huergo, Estefania; Apellániz-Ruiz, María; Urrutia-Lafuente, Edurne; Miranda, María; Salgado, Josefa; Pasalodos-Sanchez, Sara; Delgado-Mora, Luna; Teijido, Óscar; Goicoechea, Ibai; Carmona, Rosario; Perez-Florido, Javier; et al. (Genes (Basel), 2024)
Large-scale genomic studies have significantly increased our knowledge of genetic variability across populations. Regional genetic profiling is essential for distinguishing common benign variants from disease-causing ones. To this end, we conducted a comprehensive characterization of exonic variants in the population of Navarre (Spain), utilizing whole genome sequencing data from 358 unrelated individuals of Spanish origin. Our analysis revealed 61,410 biallelic single nucleotide variants (SNV) within the Navarrese cohort, with 35% classified as common (MAF > 1%). By comparing allele frequency data from 1000 Genome Project (excluding the Iberian cohort of Spain, IBS), Genome Aggregation Database, and a Spanish cohort (including IBS individuals and data from Medical Genome Project), we identified 1069 SNVs common in Navarre but rare (MAF ≤ 1%) in all other populations. We further corroborated this observation with a second regional cohort of 239 unrelated exomes, which confirmed 676 of the 1069 SNVs as common in Navarre. In conclusion, this study highlights the importance of population-specific characterization of genetic variation to improve allele frequency filtering in sequencing data analysis to identify disease-causing variants.
Keywords: Cohort Studies; Exome; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Male; Polymorphism, Single Nucleotide; Spain; Whole Genome Sequencing

Drug-target identification in COVID-19 disease mechanisms using computational systems biology approaches. - Niarakis, Anna; Ostaszewski, Marek; Mazein, Alexander; Kuperstein, Inna; Kutmon, Martina; Gillespie, Marc E; Funahashi, Akira; Acencio, Marcio Luis; Hemedan, Ahmed; Aichem, Michael; Klein, Karsten; Czauderna, Tobias; et al. (Front Immunol, 2024)
INTRODUCTION: The COVID-19 Disease Map project is a large-scale community effort uniting 277 scientists from 130 Institutions around the globe. We use high-quality, mechanistic content describing SARS-CoV-2-host interactions and develop interoperable bioinformatic pipelines for novel target identification and drug repurposing. METHODS: Extensive community work allowed an impressive step forward in building interfaces between Systems Biology tools and platforms. Our framework can link biomolecules from omics data analysis and computational modelling to dysregulated pathways in a cell-, tissue- or patient-specific manner. Drug repurposing using text mining and AI-assisted analysis identified potential drugs, chemicals and microRNAs that could target the identified key factors. RESULTS: Results revealed drugs already tested for anti-COVID-19 efficacy, providing a mechanistic context for their mode of action, and drugs already in clinical trials for treating other diseases, never tested against COVID-19. DISCUSSION: The key advance is that the proposed framework is versatile and expandable, offering a significant upgrade in the arsenal for virus-host interactions and other complex pathologies.
Keywords: Computer Simulation; COVID-19; drug repositioning; Humans; SARS-CoV-2; Systems biology

Genotypic characterization and antimicrobial susceptibility of human isolates in Southern Spain. - Fernández-Palacios, Pablo; Galán-Sánchez, Fátima; Casimiro-Soriguer, Carlos S; Jurado-Tarifa, Estefanía; Arroyo, Federico; Lara, María; Chaves, J Alberto; Dopazo, Joaquin; Rodriguez-Iglesias, Manuel A (Microbiol Spectr, 2024)
is the main cause of bacterial gastroenteritis and a public health problem worldwide. Little information is available on the genotypic characteristics of human in Spain. This study is based on an analysis of the resistome, virulome, and phylogenetic relationship, antibiogram prediction, and antimicrobial susceptibility of 114 human isolates of from a tertiary hospital in southern Spain from October 2020 to June 2023. The isolates were sequenced using Illumina technology, and a bioinformatic analysis was subsequently performed. The susceptibility of isolates to ciprofloxacin, tetracycline, and erythromycin was also tested. The resistance rates for each antibiotic were 90.3% for ciprofloxacin, 66.7% for tetracycline, and 0.88% for erythromycin. The fluoroquinolone resistance rate obtained is well above the European average (69.1%). CC-21 ( = 23), ST-572 ( = 13), and ST-6532 ( = 13) were the most prevalent clonal complexes (CCs) and sequence types (STs). In the virulome, the , and genes were detected in all the isolates. A prevalence of 20.1% was obtained for the genes and , which are related to the pathogenesis of Guillain-Barré syndrome (GBS). The prevalence of the main antimicrobial resistance markers detected were CmeABC (92.1%), RE-cmeABC (7.9%), the T86I substitution in (88.9%), (72.6%) (65.8%), and (17.1%). High antibiogram prediction rates (>97%) were obtained, except for in the case of the erythromycin-resistant phenotype. This study contributes significantly to the knowledge of genomics for the prevention, treatment, and control of infections caused by this pathogen.IMPORTANCEDespite being the pathogen with the greatest number of gastroenteritis cases worldwide, remains a poorly studied microorganism. A sustained increase in fluoroquinolone resistance in human isolates is a problem when treating infections. The development of whole genome sequencing (WGS) techniques has allowed us to better understand the genotypic characteristics of this pathogen and relate them to antibiotic resistance phenotypes. These techniques complement the data obtained from the phenotypic analysis of isolates. The zoonotic transmission of through the consumption of contaminated poultry supports approaching the study of this pathogen through "One Health" approach. In addition, due to the limited information on the genomic characteristics of in Spain, this study provides important data and allows us to compare the results with those obtained in other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Anti-Bacterial Agents; Campylobacter Infections; Campylobacter jejuni; Child; Child, Preschool; Ciprofloxacin; Drug Resistance, Bacterial; Erythromycin; Female; Genotype; Humans; Infant; Male; Microbial Sensitivity Tests; Middle Aged; Phylogeny; Spain; Tetracycline; Young Adult

HMGA1 regulates trabectedin sensitivity in advanced soft-tissue sarcoma (STS): A Spanish Group for Research on Sarcomas (GEIS) study. - Moura, David S; Mondaza-Hernandez, Jose L; Sanchez-Bustos, Paloma; Peña-Chilet, Maria; Cordero-Varela, Juan A; Lopez-Alvarez, Maria; Carrillo-Garcia, Jaime; Martin-Ruiz, Marta; Romero-Gonzalez, Pablo; Renshaw-Calderon, Marta; Ramos, Rafael; Marcilla, David; et al. (Cell Mol Life Sci, 2024)
HMGA1 is a structural epigenetic chromatin factor that has been associated with tumor progression and drug resistance. Here, we reported the prognostic/predictive value of HMGA1 for trabectedin in advanced soft-tissue sarcoma (STS) and the effect of inhibiting HMGA1 or the mTOR downstream pathway in trabectedin activity. The prognostic/predictive value of HMGA1 expression was assessed in a cohort of 301 STS patients at mRNA (n = 133) and protein level (n = 272), by HTG EdgeSeq transcriptomics and immunohistochemistry, respectively. The effect of HMGA1 silencing on trabectedin activity and gene expression profiling was measured in leiomyosarcoma cells. The effect of combining mTOR inhibitors with trabectedin was assessed on cell viability in vitro studies, whereas in vivo studies tested the activity of this combination. HMGA1 mRNA and protein expression were significantly associated with worse progression-free survival of trabectedin and worse overall survival in STS. HMGA1 silencing sensitized leiomyosarcoma cells for trabectedin treatment, reducing the spheroid area and increasing cell death. The downregulation of HGMA1 significantly decreased the enrichment of some specific gene sets, including the PI3K/AKT/mTOR pathway. The inhibition of mTOR, sensitized leiomyosarcoma cultures for trabectedin treatment, increasing cell death. In in vivo studies, the combination of rapamycin with trabectedin downregulated HMGA1 expression and stabilized tumor growth of 3-methylcholantrene-induced sarcoma-like models. HMGA1 is an adverse prognostic factor for trabectedin treatment in advanced STS. HMGA1 silencing increases trabectedin efficacy, in part by modulating the mTOR signaling pathway. Trabectedin plus mTOR inhibitors are active in preclinical models of sarcoma, downregulating HMGA1 expression levels and stabilizing tumor growth.
Keywords: Animals; Antineoplastic Agents, Alkylating; Cell Line, Tumor; Drug Resistance, Neoplasm; Female; Gene Expression Regulation, Neoplastic; HMGA1a Protein; Humans; Leiomyosarcoma; Mice; Prognosis; Sarcoma; Signal Transduction; TOR Serine-Threonine Kinases; Trabectedin; Xenograft Model Antitumor Assays

The integrated genomic surveillance system of Andalusia (SIEGA) provides a One Health regional resource connected with the clinic. - Casimiro-Soriguer, Carlos S; Perez-Florido, Javier; Robles, Enrique A; Lara, María; Aguado, Andrea; Rodríguez Iglesias, Manuel A; Lepe, Jose A; García, Federico; Pérez-Alegre, Mónica; Andújar, Eloísa; Jiménez, Victoria E; Camino, Lola P; et al. (Sci Rep, 2024)
The One Health approach, recognizing the interconnectedness of human, animal, and environmental health, has gained significance amid emerging zoonotic diseases and antibiotic resistance concerns. This paper aims to demonstrate the utility of a collaborative tool, the SIEGA, for monitoring infectious diseases across domains, fostering a comprehensive understanding of disease dynamics and risk factors, highlighting the pivotal role of One Health surveillance systems. Raw whole-genome sequencing is processed through different species-specific open software that additionally reports the presence of genes associated to anti-microbial resistances and virulence. The SIEGA application is a Laboratory Information Management System, that allows customizing reports, detect transmission chains, and promptly alert on alarming genetic similarities. The SIEGA initiative has successfully accumulated a comprehensive collection of more than 1900 bacterial genomes, including Salmonella enterica, Listeria monocytogenes, Campylobacter jejuni, Escherichia coli, Yersinia enterocolitica and Legionella pneumophila, showcasing its potential in monitoring pathogen transmission, resistance patterns, and virulence factors. SIEGA enables customizable reports and prompt detection of transmission chains, highlighting its contribution to enhancing vigilance and response capabilities. Here we show the potential of genomics in One Health surveillance when supported by an appropriate bioinformatic tool. By facilitating precise disease control strategies and antimicrobial resistance management, SIEGA enhances global health security and reduces the burden of infectious diseases. The integration of health data from humans, animals, and the environment, coupled with advanced genomics, underscores the importance of a holistic One Health approach in mitigating health threats.
Keywords: Animals; Drug Resistance, Bacterial; Genome, Bacterial; Genomics; Humans; One Health; Virulence Factors; Whole Genome Sequencing

Shared germline genomic variants in two patients with double primary gastrointestinal stromal tumours (GISTs). - Moura, David S; López López, Daniel; di Lernia, Davide; Martin-Ruiz, Marta; Lopez-Alvarez, Maria; Ramos, Rafael; Merino, Jose; Dopazo, Joaquin; Lopez-Guerrero, Jose; Mondaza-Hernandez, Jose L; Romero, Pablo; Hindi, Nadia; et al. (J Med Genet, 2024)
BACKGROUND: Gastrointestinal stromal tumours (GISTs) are prevalent mesenchymal tumours of the gastrointestinal tract, commonly exhibiting structural variations in and genes. While the mutational profiling of somatic tumours is well described, the genes behind the susceptibility to develop GIST are not yet fully discovered. This study explores the genomic landscape of two primary GIST cases, aiming to identify shared germline pathogenic variants and shed light on potential key players in tumourigenesis. METHODS: Two patients with distinct genotypically and phenotypically GISTs underwent germline whole genome sequencing. CNV and single nucleotide variant (SNV) analyses were performed. RESULTS: Both patients harbouring low-risk GISTs with different mutations ( and ) shared homozygous germline pathogenic deletions in both and genes. CNV analysis revealed additional shared pathogenic deletions in other genes such as . No particular pathogenic SNV shared by both patients was detected. CONCLUSION: Our study provides new insights into germline variants that can be associated with the development of GISTs, namely, and deep deletions. Further functional validation is warranted to elucidate the precise contributions of identified germline mutations in GIST development.
Keywords: DNA Copy Number Variations; Female; Gastrointestinal Neoplasms; Gastrointestinal Stromal Tumors; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins c-kit; Receptor, Platelet-Derived Growth Factor alpha; Whole Genome Sequencing

Evaluation of a combined detection of SARS-CoV-2 and its variants using real-time allele-specific PCR strategy: an advantage for clinical practice. - Chaves-Blanco, Lucía; de Salazar, Adolfo; Fuentes, Ana; Viñuela, Laura; Perez-Florido, Javier; Dopazo, Joaquin; García, Federico (Epidemiol Infect, 2023)
This study aimed to assess the ability of a real-time reverse transcription polymerase chain reaction (RT-PCR) with multiple targets to detect SARS-CoV-2 and its variants in a single test. Nasopharyngeal specimens were collected from patients in Granada, Spain, between January 2021 and December 2022. Five allele-specific RT-PCR kits were used sequentially, with each kit designed to detect a predominant variant at the time. When the Alpha variant was dominant, the kit included the HV69/70 deletion, E and N genes. When Delta replaced Alpha, the kit incorporated the L452R mutation in addition to E and N genes. When Omicron became dominant, L452R was replaced with the N679K mutation. Before incorporating each variant kit, a comparative analysis was carried out with SARS-CoV-2 whole genome sequencing (WGS). The results demonstrated that RT-PCR with multiple targets can provide rapid and effective detection of SARS-CoV-2 and its variants in a single test. A very high degree of agreement (96.2%) was obtained between the comparison of RT-PCR and WGS. Allele-specific RT-PCR assays make it easier to implement epidemiological surveillance systems for effective public health decision making.
Keywords: Alleles; COVID-19; COVID-19 Testing; Humans; Real-Time Polymerase Chain Reaction; SARS-CoV-2; Sensitivity and Specificity

Assessing the Impact of SARS-CoV-2 Lineages and Mutations on Patient Survival. - Loucera, Carlos; Perez-Florido, Javier; Casimiro-Soriguer, Carlos S; Ortuno, Francisco M; Carmona, Rosario; Bostelmann, Gerrit; Martínez-González, L Javier; Muñoyerro-Muñiz, Dolores; Villegas, Román; Rodríguez-Baño, Jesús; Romero-Gómez, Manuel; Lorusso, Nicola; et al. (Viruses, 2022)
OBJECTIVES: More than two years into the COVID-19 pandemic, SARS-CoV-2 still remains a global public health problem. Successive waves of infection have produced new SARS-CoV-2 variants with new mutations for which the impact on COVID-19 severity and patient survival is uncertain. METHODS: A total of 764 SARS-CoV-2 genomes, sequenced from COVID-19 patients, hospitalized from 19th February 2020 to 30 April 2021, along with their clinical data, were used for survival analysis. RESULTS: A significant association of B.1.1.7, the alpha lineage, with patient mortality (log hazard ratio (LHR) = 0.51, C.I. = [0.14,0.88]) was found upon adjustment by all the covariates known to affect COVID-19 prognosis. Moreover, survival analysis of mutations in the SARS-CoV-2 genome revealed 27 of them were significantly associated with higher mortality of patients. Most of these mutations were located in the genes coding for the S, ORF8, and N proteins. CONCLUSIONS: This study illustrates how a combination of genomic and clinical data can provide solid evidence for the impact of viral lineage on patient survival.
Keywords: COVID-19; Genome, Viral; Humans; mutation; Pandemics; Phylogeny; SARS-CoV-2

Endoglin and MMP14 Contribute to Ewing Sarcoma Spreading by Modulation of Cell-Matrix Interactions. - Puerto-Camacho, Pilar; Diaz-Martin, Juan; Olmedo-Pelayo, Joaquín; Bolado-Carrancio, Alfonso; Salguero-Aranda, Carmen; Jordán-Pérez, Carmen; Esteban-Medina, Marina; Alamo-Alvarez, Inmaculada; Delgado-Bellido, Daniel; Lobo-Selma, Laura; Dopazo, Joaquin; Sastre, Ana; et al. (Int J Mol Sci, 2022)
Endoglin (ENG) is a mesenchymal stem cell (MSC) marker typically expressed by active endothelium. This transmembrane glycoprotein is shed by matrix metalloproteinase 14 (MMP14). Our previous work demonstrated potent preclinical activity of first-in-class anti-ENG antibody-drug conjugates as a nascent strategy to eradicate Ewing sarcoma (ES), a devastating rare bone/soft tissue cancer with a putative MSC origin. We also defined a correlation between ENG and MMP14 expression in ES. Herein, we show that ENG expression is significantly associated with a dismal prognosis in a large cohort of ES patients. Moreover, both ENG/MMP14 are frequently expressed in primary ES tumors and metastasis. To deepen in their functional relevance in ES, we conducted transcriptomic and proteomic profiling of in vitro ES models that unveiled a key role of ENG and MMP14 in cell mechano-transduction. Migration and adhesion assays confirmed that loss of ENG disrupts actin filament assembly and filopodia formation, with a concomitant effect on cell spreading. Furthermore, we observed that ENG regulates cell-matrix interaction through activation of focal adhesion signaling and protein kinase C expression. In turn, loss of MMP14 contributed to a more adhesive phenotype of ES cells by modulating the transcriptional extracellular matrix dynamics. Overall, these results suggest that ENG and MMP14 exert a significant role in mediating correct spreading machinery of ES cells, impacting the aggressiveness of the disease.
Keywords: Bone Neoplasms; Endoglin; Humans; Matrix Metalloproteinase 14; Proteomics; Receptors, Growth Factor; Sarcoma, Ewing; Signal Transduction

A comprehensive database for integrated analysis of omics data in autoimmune diseases. - Martorell-Marugán, Jordi; López-Domínguez, Raúl; García-Moreno, Adrián; Toro-Domínguez, Daniel; Villatoro-García, Juan Antonio; Barturen, Guillermo; Martín-Gómez, Adoración; Troule, Kevin; Gómez-López, Gonzalo; Al-Shahrour, Fátima; González-Rumayor, Víctor; Peña-Chilet, Maria; et al. (BMC Bioinformatics, 2021)
BACKGROUND: Autoimmune diseases are heterogeneous pathologies with difficult diagnosis and few therapeutic options. In the last decade, several omics studies have provided significant insights into the molecular mechanisms of these diseases. Nevertheless, data from different cohorts and pathologies are stored independently in public repositories and a unified resource is imperative to assist researchers in this field. RESULTS: Here, we present Autoimmune Diseases Explorer ( https://adex.genyo.es ), a database that integrates 82 curated transcriptomics and methylation studies covering 5609 samples for some of the most common autoimmune diseases. The database provides, in an easy-to-use environment, advanced data analysis and statistical methods for exploring omics datasets, including meta-analysis, differential expression or pathway analysis. CONCLUSIONS: This is the first omics database focused on autoimmune diseases. This resource incorporates homogeneously processed data to facilitate integrative analyses among studies.
Keywords: Autoimmune Diseases; Computational Biology; Databases, Factual; Humans

COVID19 Disease Map, a computational knowledge repository of virus-host interaction mechanisms. - Ostaszewski, Marek; Niarakis, Anna; Mazein, Alexander; Kuperstein, Inna; Phair, Robert; Orta-Resendiz, Aurelio; Singh, Vidisha; Aghamiri, Sara Sadat; Acencio, Marcio Luis; Glaab, Enrico; Ruepp, Andreas; Fobo, Gisela; et al. (Mol Syst Biol, 2021)
We need to effectively combine the knowledge from surging literature with complex datasets to propose mechanistic models of SARS-CoV-2 infection, improving data interpretation and predicting key targets of intervention. Here, we describe a large-scale community effort to build an open access, interoperable and computable repository of COVID-19 molecular mechanisms. The COVID-19 Disease Map (C19DMap) is a graphical, interactive representation of disease-relevant molecular mechanisms linking many knowledge sources. Notably, it is a computational resource for graph-based analyses and disease modelling. To this end, we established a framework of tools, platforms and guidelines necessary for a multifaceted community of biocurators, domain experts, bioinformaticians and computational biologists. The diagrams of the C19DMap, curated from the literature, are integrated with relevant interaction and text mining databases. We demonstrate the application of network analysis and modelling approaches by concrete examples to highlight new testable hypotheses. This framework helps to find signatures of SARS-CoV-2 predisposition, treatment response or prioritisation of drug candidates. Such an approach may help deal with new waves of COVID-19 or similar pandemics in the long-term perspective.
Keywords: Antiviral Agents; Computational Biology; Computer Graphics; COVID-19; Cytokines; Data Mining; Databases, Factual; Gene Expression Regulation; Host Microbial Interactions; Humans; Immunity, Cellular; Immunity, Humoral; Immunity, Innate; Lymphocytes; Metabolic Networks and Pathways; Myeloid Cells; Protein Interaction Mapping; SARS-CoV-2; Signal Transduction; Software; Transcription Factors; Viral Proteins

CSVS, a crowdsourcing database of the Spanish population genetic variability. - Peña-Chilet, Maria; Roldán, Gema; Perez-Florido, Javier; Ortuno, Francisco M; Carmona, Rosario; Aquino, Virginia; López-López, Daniel; Loucera, Carlos; Fernandez-Rueda, Jose L; Gallego, Asunción; Garcia-Garcia, Francisco; González-Neira, Anna; et al. (Nucleic Acids Res, 2021)
The knowledge of the genetic variability of the local population is of utmost importance in personalized medicine and has been revealed as a critical factor for the discovery of new disease variants. Here, we present the Collaborative Spanish Variability Server (CSVS), which currently contains more than 2000 genomes and exomes of unrelated Spanish individuals. This database has been generated in a collaborative crowdsourcing effort collecting sequencing data produced by local genomic projects and for other purposes. Sequences have been grouped by ICD10 upper categories. A web interface allows querying the database removing one or more ICD10 categories. In this way, aggregated counts of allele frequencies of the pseudo-control Spanish population can be obtained for diseases belonging to the category removed. Interestingly, in addition to pseudo-control studies, some population studies can be made, as, for example, prevalence of pharmacogenomic variants, etc. In addition, this genomic data has been used to define the first Spanish Genome Reference Panel (SGRP1.0) for imputation. This is the first local repository of variability entirely produced by a crowdsourcing effort and constitutes an example for future initiatives to characterize local variability worldwide. CSVS is also part of the GA4GH Beacon network. CSVS can be accessed at: http://csvs.babelomics.org/.
Keywords: Alleles; Chromosome Mapping; Crowdsourcing; Databases, Genetic; Exome; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Internet; Precision Medicine; Software; Spain

Real world evidence of calcifediol or vitamin D prescription and mortality rate of COVID-19 in a retrospective cohort of hospitalized Andalusian patients. - Loucera, Carlos; Peña-Chilet, Maria; Esteban-Medina, Marina; Muñoyerro-Muñiz, Dolores; Villegas, Román; López-Miranda, José; Rodríguez-Baño, Jesús; Túnez, Isaac; Bouillon, Roger; Dopazo, Joaquin; Quesada Gomez, Jose Manuel (Sci Rep, 2021)
COVID-19 is a major worldwide health problem because of acute respiratory distress syndrome, and mortality. Several lines of evidence have suggested a relationship between the vitamin D endocrine system and severity of COVID-19. We present a survival study on a retrospective cohort of 15,968 patients, comprising all COVID-19 patients hospitalized in Andalusia between January and November 2020. Based on a central registry of electronic health records (the Andalusian Population Health Database, BPS), prescription of vitamin D or its metabolites within 15-30 days before hospitalization were recorded. The effect of prescription of vitamin D (metabolites) for other indication previous to the hospitalization was studied with respect to patient survival. Kaplan-Meier survival curves and hazard ratios support an association between prescription of these metabolites and patient survival. Such association was stronger for calcifediol (Hazard Ratio, HR = 0.67, with 95% confidence interval, CI, of [0.50-0.91]) than for cholecalciferol (HR = 0.75, with 95% CI of [0.61-0.91]), when prescribed 15 days prior hospitalization. Although the relation is maintained, there is a general decrease of this effect when a longer period of 30 days prior hospitalization is considered (calcifediol HR = 0.73, with 95% CI [0.57-0.95] and cholecalciferol HR = 0.88, with 95% CI [0.75, 1.03]), suggesting that association was stronger when the prescription was closer to the hospitalization.
Keywords: Calcifediol; COVID-19; Female; Humans; Kaplan-Meier Estimate; Male; Retrospective Studies; Spain; Survival Analysis; Vitamin D

Reporting guidelines for human microbiome research: the STORMS checklist. - Mirzayi, Chloe; Renson, Audrey; Zohra, Fatima; Elsafoury, Shaimaa; Geistlinger, Ludwig; Kasselman, Lora J; Eckenrode, Kelly; van de Wijgert, Janneke; Loughman, Amy; Marques, Francine Z; MacIntyre, David A; Arumugam, Manimozhiyan; et al. (Nat Med, 2021)
The particularly interdisciplinary nature of human microbiome research makes the organization and reporting of results spanning epidemiology, biology, bioinformatics, translational medicine and statistics a challenge. Commonly used reporting guidelines for observational or genetic epidemiology studies lack key features specific to microbiome studies. Therefore, a multidisciplinary group of microbiome epidemiology researchers adapted guidelines for observational and genetic studies to culture-independent human microbiome studies, and also developed new reporting elements for laboratory, bioinformatics and statistical analyses tailored to microbiome studies. The resulting tool, called 'Strengthening The Organization and Reporting of Microbiome Studies' (STORMS), is composed of a 17-item checklist organized into six sections that correspond to the typical sections of a scientific publication, presented as an editable table for inclusion in supplementary materials. The STORMS checklist provides guidance for concise and complete reporting of microbiome studies that will facilitate manuscript preparation, peer review, and reader comprehension of publications and comparative analysis of published results.
Keywords: Computational Biology; Dysbiosis; Humans; Microbiota; Observational Studies as Topic; Research Design; Translational Science, Biomedical

Taxonomic variations in the gut microbiome of gout patients with and without tophi might have a functional impact on urate metabolism. - Méndez-Salazar, Eder Orlando; Vázquez-Mellado, Janitzia; Casimiro-Soriguer, Carlos S; Dopazo, Joaquin; Cubuk, Cankut; Zamudio-Cuevas, Yessica; Francisco-Balderas, Adriana; Martínez-Flores, Karina; Fernández-Torres, Javier; Lozada-Pérez, Carlos; Pineda, Carlos; Sánchez-González, Austreberto; et al. (Mol Med, 2021)
OBJECTIVE: To evaluate the taxonomic composition of the gut microbiome in gout patients with and without tophi formation, and predict bacterial functions that might have an impact on urate metabolism. METHODS: Hypervariable V3-V4 regions of the bacterial 16S rRNA gene from fecal samples of gout patients with and without tophi (n = 33 and n = 25, respectively) were sequenced and compared to fecal samples from 53 healthy controls. We explored predictive functional profiles using bioinformatics in order to identify differences in taxonomy and metabolic pathways. RESULTS: We identified a microbiome characterized by the lowest richness and a higher abundance of Phascolarctobacterium, Bacteroides, Akkermansia, and Ruminococcus_gnavus_group genera in patients with gout without tophi when compared to controls. The Proteobacteria phylum and the Escherichia-Shigella genus were more abundant in patients with tophaceous gout than in controls. Fold change analysis detected nine genera enriched in healthy controls compared to gout groups (Bifidobacterium, Butyricicoccus, Oscillobacter, Ruminococcaceae_UCG_010, Lachnospiraceae_ND2007_group, Haemophilus, Ruminococcus_1, Clostridium_sensu_stricto_1, and Ruminococcaceae_UGC_013). We found that the core microbiota of both gout groups shared Bacteroides caccae, Bacteroides stercoris ATCC 43183, and Bacteroides coprocola DSM 17136. These bacteria might perform functions linked to one-carbon metabolism, nucleotide binding, amino acid biosynthesis, and purine biosynthesis. Finally, we observed differences in key bacterial enzymes involved in urate synthesis, degradation, and elimination. CONCLUSION: Our findings revealed that taxonomic variations in the gut microbiome of gout patients with and without tophi might have a functional impact on urate metabolism.
Keywords: Biodiversity; Computational Biology; Dysbiosis; Gastrointestinal Microbiome; Gout; Humans; Metagenome; metagenomics; Protein Interaction Mapping; Protein Interaction Maps; Uric Acid

A versatile workflow to integrate RNA-seq genomic and transcriptomic data into mechanistic models of signaling pathways. - Garrido-Rodriguez, Martín; López-López, Daniel; Ortuno, Francisco M; Peña-Chilet, Maria; Muñoz, Eduardo; Calzado, Marco A; Dopazo, Joaquin (PLoS Comput Biol, 2021)
MIGNON is a workflow for the analysis of RNA-Seq experiments, which not only efficiently manages the estimation of gene expression levels from raw sequencing reads, but also calls genomic variants present in the transcripts analyzed. Moreover, this is the first workflow that provides a framework for the integration of transcriptomic and genomic data based on a mechanistic model of signaling pathway activities that allows a detailed biological interpretation of the results, including a comprehensive functional profiling of cell activity. MIGNON covers the whole process, from reads to signaling circuit activity estimations, using state-of-the-art tools, it is easy to use and it is deployable in different computational environments, allowing an optimized use of the resources available.
Keywords: Algorithms; Cell Line, Tumor; Computational Biology; Databases, Factual; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Models, Theoretical; mutation; RNA-seq; Signal Transduction; Software; Transcriptome; whole exome sequencing; Workflow

COVID-19 Disease Map, building a computational repository of SARS-CoV-2 virus-host interaction mechanisms. - Ostaszewski, Marek; Mazein, Alexander; Gillespie, Marc E; Kuperstein, Inna; Niarakis, Anna; Hermjakob, Henning; Pico, Alexander R; Willighagen, Egon L; Evelo, Chris T; Hasenauer, Jan; Schreiber, Falk; Dräger, Andreas; et al. (Sci Data, 2020)
Keywords: Betacoronavirus; Computational Biology; Coronavirus Infections; COVID-19; Databases, Factual; Host Microbial Interactions; Host-Pathogen Interactions; Humans; International Cooperation; Models, Biological; Pandemics; Pneumonia, Viral; SARS-CoV-2

Drug repurposing for COVID-19 using machine learning and mechanistic models of signal transduction circuits related to SARS-CoV-2 infection. - Loucera, Carlos; Esteban-Medina, Marina; Rian, Kinza; Falco, Matias M; Dopazo, Joaquin; Peña-Chilet, Maria (Signal Transduct Target Ther, 2020)
Keywords: Computational Chemistry; COVID-19; drug repositioning; Humans; Machine Learning; Molecular Docking Simulation; Molecular Targeted Therapy; Proteins; SARS-CoV-2; Signal Transduction

The ELIXIR Human Copy Number Variations Community: building bioinformatics infrastructure for research. - Salgado, David; Armean, Irina M; Baudis, Michael; Beltran, Sergi; Capella-Gutíerrez, Salvador; Carvalho-Silva, Denise; Dominguez Del Angel, Victoria; Dopazo, Joaquin; Furlong, Laura I; Gao, Bo; Garcia, Leyla; Gerloff, Dietlind; et al. (F1000Res, 2020)
Copy number variations (CNVs) are major causative contributors both in the genesis of genetic diseases and human neoplasias. While "High-Throughput" sequencing technologies are increasingly becoming the primary choice for genomic screening analysis, their ability to efficiently detect CNVs is still heterogeneous and remains to be developed. The aim of this white paper is to provide a guiding framework for the future contributions of ELIXIR's recently established with implications beyond human disease diagnostics and population genomics. This white paper is the direct result of a strategy meeting that took place in September 2018 in Hinxton (UK) and involved representatives of 11 ELIXIR Nodes. The meeting led to the definition of priority objectives and tasks, to address a wide range of CNV-related challenges ranging from detection and interpretation to sharing and training. Here, we provide suggestions on how to align these tasks within the ELIXIR Platforms strategy, and on how to frame the activities of this new ELIXIR Community in the international context.
Keywords: Computational Biology; DNA Copy Number Variations; High-Throughput Nucleotide Sequencing; Humans

[Impact assessment on data protection in research projects]. - García-León, Francisco Javier; Villegas-Portero, Román; Goicoechea-Salazar, Juan Antonio; Muñoyerro-Muñiz, Dolores; Dopazo, Joaquin (Gac Sanit, 2020)
Recent changes in European regulations for personal data protection still allow the use of health data for research purposes, but they have set the Impact Assessment on Data Protection as an instrument for reflection and risk analysis in the process of data processing. The publication of a guide for facilitates this impact assessment, although it is not directly applicable to research projects. Experience in a specific project is detailed, showing how the context of the treatment becomes relevant with respect to the data characteristics. Carrying out an impact assessment is an opportunity to ensure compliance with the principles of data protection in an increasingly complex environment with greater ethical challenges.
Keywords: Computer Security; Humans

Mechanistic Models of Signaling Pathways Reveal the Drug Action Mechanisms behind Gender-Specific Gene Expression for Cancer Treatments. - Cubuk, Cankut; Can, Fatma E; Peña-Chilet, Maria; Dopazo, Joaquin (Cells, 2020)
Despite the existence of differences in gene expression across numerous genes between males and females having been known for a long time, these have been mostly ignored in many studies, including drug development and its therapeutic use. In fact, the consequences of such differences over the disease mechanisms or the drug action mechanisms are completely unknown. Here we applied mechanistic mathematical models of signaling activity to reveal the ultimate functional consequences that gender-specific gene expression activities have over cell functionality and fate. Moreover, we also used the mechanistic modeling framework to simulate the drug interventions and unravel how drug action mechanisms are affected by gender-specific differential gene expression. Interestingly, some cancers have many biological processes significantly affected by these gender-specific differences (e.g., bladder or head and neck carcinomas), while others (e.g., glioblastoma or rectum cancer) are almost insensitive to them. We found that many of these gender-specific differences affect cancer-specific pathways or in physiological signaling pathways, also involved in cancer origin and development. Finally, mechanistic models have the potential to be used for finding alternative therapeutic interventions on the pathways targeted by the drug, which lead to similar results compensating the downstream consequences of gender-specific differences in gene expression.
Keywords: Female; Gene Expression Regulation, Neoplastic; Humans; Male; Neoplasms; Signal Transduction

Nivolumab and sunitinib combination in advanced soft tissue sarcomas: a multicenter, single-arm, phase Ib/II trial. - Martin-Broto, Javier; Hindi, Nadia; Grignani, Giovanni; Martinez-Trufero, Javier; Redondo, Andres; Valverde, Claudia; Stacchiotti, Silvia; Lopez-Pousa, Antonio; D'Ambrosio, Lorenzo; Gutierrez, Antonio; Perez-Vega, Herminia; Encinas-Tobajas, Victor; et al. (J Immunother Cancer, 2020)
BACKGROUND: Sarcomas exhibit low expression of factors related to immune response, which could explain the modest activity of PD-1 inhibitors. A potential strategy to convert a cold into an inflamed microenvironment lies on a combination therapy. As tumor angiogenesis promotes immunosuppression, we designed a phase Ib/II trial to test the double inhibition of angiogenesis (sunitinib) and PD-1/PD-L1 axis (nivolumab). METHODS: This single-arm, phase Ib/II trial enrolled adult patients with selected subtypes of sarcoma. Phase Ib established two dose levels: level 0 with sunitinib 37.5 mg daily from day 1, plus nivolumab 3 mg/kg intravenously on day 15, and then every 2 weeks; and level -1 with sunitinib 37.5 mg on the first 14 days (induction) and then 25 mg per day plus nivolumab on the same schedule. The primary endpoint was to determine the recommended dose for phase II (phase I) and the 6-month progression-free survival rate, according to Response Evaluation Criteria in Solid Tumors 1.1 (phase II). RESULTS: From May 2017 to April 2019, 68 patients were enrolled: 16 in phase Ib and 52 in phase II. The recommended dose of sunitinib for phase II was 37.5 mg as induction and then 25 mg in combination with nivolumab. After a median follow-up of 17 months (4-26), the 6-month progression-free survival rate was 48% (95% CI 41% to 55%). The most common grade 3-4 adverse events included transaminitis (17.3%) and neutropenia (11.5%). CONCLUSIONS: Sunitinib plus nivolumab is an active scheme with manageable toxicity in the treatment of selected patients with advanced soft tissue sarcoma, with almost half of patients free of progression at 6 months. NCT03277924.
Keywords: Adult; Aged; Antineoplastic Agents, Immunological; Female; Humans; Male; Middle Aged; Nivolumab; Sarcoma; Sunitinib; Young Adult

Optimised molecular genetic diagnostics of Fanconi anaemia by whole exome sequencing and functional studies. - Bogliolo, Massimo; Pujol, Roser; Aza-Carmona, Miriam; Muñoz-Subirana, Núria; Rodriguez-Santiago, Benjamin; Casado, José Antonio; Rio, Paula; Bauser, Christopher; Reina-Castillón, Judith; Lopez-Sanchez, Marcos; Gonzalez-Quereda, Lidia; Gallano, Pia; et al. (J Med Genet, 2020)
PURPOSE: Patients with Fanconi anaemia (FA), a rare DNA repair genetic disease, exhibit chromosome fragility, bone marrow failure, malformations and cancer susceptibility. FA molecular diagnosis is challenging since FA is caused by point mutations and large deletions in 22 genes following three heritability patterns. To optimise FA patients' characterisation, we developed a simplified but effective methodology based on whole exome sequencing (WES) and functional studies. METHODS: 68 patients with FA were analysed by commercial WES services. Copy number variations were evaluated by sequencing data analysis with RStudio. To test missense variants, wt FANCA cDNA was cloned and variants were introduced by site-directed mutagenesis. Vectors were then tested for their ability to complement DNA repair defects of a FANCA-KO human cell line generated by TALEN technologies. RESULTS: We identified 93.3% of mutated alleles including large deletions. We determined the pathogenicity of three FANCA missense variants and demonstrated that two variants reported in mutations databases as 'affecting functions' are SNPs. Deep analysis of sequencing data revealed patients' true mutations, highlighting the importance of functional analysis. In one patient, no pathogenic variant could be identified in any of the 22 known FA genes, and in seven patients, only one deleterious variant could be identified (three patients each with FANCA and FANCD2 and one patient with FANCE mutations) CONCLUSION: WES and proper bioinformatics analysis are sufficient to effectively characterise patients with FA regardless of the rarity of their complementation group, type of mutations, mosaic condition and DNA source.
Keywords: Cell Line; DNA Copy Number Variations; DNA Repair; DNA-Binding Proteins; Fanconi Anemia; Fanconi Anemia Complementation Group A Protein; Female; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Polymorphism, Single Nucleotide; whole exome sequencing

Pazopanib for treatment of typical solitary fibrous tumours: a multicentre, single-arm, phase 2 trial. - Martin-Broto, Javier; Cruz, Josefina; Penel, Nicolas; Le Cesne, Axel; Hindi, Nadia; Luna, Pablo; Moura, David S; Bernabeu, Daniel; de Alava, Enrique; Lopez-Guerrero, Jose Antonio; Dopazo, Joaquin; Peña-Chilet, Maria; et al. (Lancet Oncol, 2020)
BACKGROUND: Solitary fibrous tumour is an ultra-rare sarcoma, which encompasses different clinicopathological subgroups. The dedifferentiated subgroup shows an aggressive course with resistance to pazopanib, whereas in the malignant subgroup, pazopanib shows higher activity than in previous studies with chemotherapy. We designed a trial to test pazopanib activity in two different cohorts of solitary fibrous tumour: the malignant-dedifferentiated cohort, which was previously published, and the typical cohort, which is presented here. METHODS: In this single-arm, phase 2 trial, adult patients (aged ≥18 years) diagnosed with confirmed metastatic or unresectable typical solitary fibrous tumour of any location, who had progressed in the previous 6 months (by Choi criteria or Response Evaluation Criteria in Solid Tumors [RECIST]) and an Eastern Cooperative Oncology Group (ECOG) performance status of 0-2 were enrolled at 11 tertiary hospitals in Italy, France, and Spain. Patients received pazopanib 800 mg once daily, taken orally, until progression, unacceptable toxicity, withdrawal of consent, non-compliance, or a delay in pazopanib administration of longer than 3 weeks. The primary endpoint was proportion of patients achieving an overall response measured by Choi criteria in patients who received at least 1 month of treatment with at least one radiological assessment. All patients who received at least one dose of the study drug were included in the safety analyses. This study is registered in ClinicalTrials.gov, NCT02066285, and with the European Clinical Trials Database, EudraCT 2013-005456-15. FINDINGS: From June 26, 2014, to Dec 13, 2018, of 40 patients who were assessed, 34 patients were enrolled and 31 patients were included in the response analysis. Median follow-up was 18 months (IQR 14-34), and 18 (58%) of 31 patients had a partial response, 12 (39%) had stable disease, and one (3%) showed progressive disease according to Choi criteria and central review. The proportion of overall response based on Choi criteria was 58% (95% CI 34-69). There were no deaths caused by toxicity, and the most frequent adverse events were diarrhoea (18 [53%] of 34 patients), fatigue (17 [50%]), and hypertension (17 [50%]). INTERPRETATION: To our knowledge, this is the first prospective trial of pazopanib for advanced typical solitary fibrous tumour. The manageable toxicity and activity shown by pazopanib in this cohort suggest that this drug could be considered as first-line treatment for advanced typical solitary fibrous tumour. FUNDING: Spanish Group for Research on Sarcomas (GEIS), Italian Sarcoma Group (ISG), French Sarcoma Group (FSG), GlaxoSmithKline, and Novartis.
Keywords: Aged; Female; Follow-Up Studies; Humans; Indazoles; Male; Middle Aged; Neoplasm Metastasis; Prognosis; Prospective Studies; Protein Kinase Inhibitors; Pyrimidines; Response Evaluation Criteria in Solid Tumors; Solitary Fibrous Tumors; Sulfonamides; Survival Rate

Platform to study intracellular polystyrene nanoplastic pollution and clinical outcomes. - Bojic, Sanja; Falco, Matias M; Stojkovic, Petra; Ljujic, Biljana; Gazdic Jankovic, Marina; Armstrong, Lyle; Markovic, Nebojsa; Dopazo, Joaquin; Lako, Majlinda; Bauer, Roman; Stojkovic, Miodrag (Stem Cells, 2020)
Increased pollution by plastics has become a serious global environmental problem, but the concerns for human health have been raised after reported presence of microplastics (MPs) and nanoplastics (NPs) in food and beverages. Unfortunately, few studies have investigate the potentially harmful effects of MPs/NPs on early human development and human health. Therefore, we used a new platform to study possible effects of polystyrene NPs (PSNPs) on the transcription profile of preimplantation human embryos and human induced pluripotent stem cells (hiPSCs). Two pluripotency genes, LEFTY1 and LEFTY2, which encode secreted ligands of the transforming growth factor-beta, were downregulated, while CA4 and OCLM, which are related to eye development, were upregulated in both samples. The gene set enrichment analysis showed that the development of atrioventricular heart valves and the dysfunction of cellular components, including extracellular matrix, were significantly affected after exposure of hiPSCs to PSNPs. Finally, using the HiPathia method, which uncovers disease mechanisms and predicts clinical outcomes, we determined the APOC3 circuit, which is responsible for increased risk for ischemic cardiovascular disease. These results clearly demonstrate that better understanding of NPs bioactivities and its implications for human health is of extreme importance. Thus, the presented platform opens further aspects to study interactions between different environmental and intracellular pollutions with the aim to decipher the mechanism and origin of human diseases.
Keywords: Environmental Pollution; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Nanoparticles; Plastics; Polystyrenes; Transcriptome; Treatment Outcome

SMN1 copy-number and sequence variant analysis from next-generation sequencing data. - López-López, Daniel; Loucera, Carlos; Carmona, Rosario; Aquino, Virginia; Salgado, Josefa; Pasalodos, Sara; Miranda, María; Alonso, Ángel; Dopazo, Joaquin (Hum Mutat, 2020)
Spinal muscular atrophy (SMA) is a severe neuromuscular autosomal recessive disorder affecting 1/10,000 live births. Most SMA patients present homozygous deletion of SMN1, while the vast majority of SMA carriers present only a single SMN1 copy. The sequence similarity between SMN1 and SMN2, and the complexity of the SMN locus makes the estimation of the SMN1 copy-number by next-generation sequencing (NGS) very difficult. Here, we present SMAca, the first python tool to detect SMA carriers and estimate the absolute SMN1 copy-number using NGS data. Moreover, SMAca takes advantage of the knowledge of certain variants specific to SMN1 duplication to also identify silent carriers. This tool has been validated with a cohort of 326 samples from the Navarra 1000 Genomes Project (NAGEN1000). SMAca was developed with a focus on execution speed and easy installation. This combination makes it especially suitable to be integrated into production NGS pipelines. Source code and documentation are available at https://www.github.com/babelomics/SMAca.
Keywords: Base Sequence; DNA Copy Number Variations; High-Throughput Nucleotide Sequencing; Humans; Reproducibility of Results; Software; Survival of Motor Neuron 1 Protein

Transcriptomic Analysis of a Diabetic Skin-Humanized Mouse Model Dissects Molecular Pathways Underlying the Delayed Wound Healing Response. - León, Carlos; Garcia-Garcia, Francisco; Llames, Sara; García-Pérez, Eva; Carretero, Marta; Arriba, María Del Carmen; Dopazo, Joaquin; Del Rio, Marcela; Escamez, Maria José; Martínez-Santamaría, Lucía (Genes (Basel), 2020)
Defective healing leading to cutaneous ulcer formation is one of the most feared complications of diabetes due to its consequences on patients' quality of life and on the healthcare system. A more in-depth analysis of the underlying molecular pathophysiology is required to develop effective healing-promoting therapies for those patients. Major architectural and functional differences with human epidermis limit extrapolation of results coming from rodents and other small mammal-healing models. Therefore, the search for reliable humanized models has become mandatory. Previously, we developed a diabetes-induced delayed humanized wound healing model that faithfully recapitulated the major histological features of such skin repair-deficient condition. Herein, we present the results of a transcriptomic and functional enrichment analysis followed by a mechanistic analysis performed in such humanized wound healing model. The deregulation of genes implicated in functions such as angiogenesis, apoptosis, and inflammatory signaling processes were evidenced, confirming published data in diabetic patients that in fact might also underlie some of the histological features previously reported in the delayed skin-humanized healing model. Altogether, these molecular findings support the utility of such preclinical model as a valuable tool to gain insight into the molecular basis of the delayed diabetic healing with potential impact in the translational medicine field.
Keywords: Animals; Diabetes Mellitus, Experimental; Gene Expression Profiling; Gene Expression Regulation; Gene ontology; Humans; Metabolic Networks and Pathways; Mice; Mice, Nude; Microarray Analysis; Molecular Sequence Annotation; Principal Component Analysis; Signal Transduction; Skin; Skin Transplantation; Skin Ulcer; Streptozocin; Tissue Engineering; Transcriptome; Transplantation, Heterologous; Wound Healing

A comparison of mechanistic signaling pathway activity analysis methods. - Amadoz, Alicia; Hidalgo, Marta R; Cubuk, Cankut; Carbonell-Caballero, José; Dopazo, Joaquin (Brief Bioinform, 2019)
Understanding the aspects of cell functionality that account for disease mechanisms or drug modes of action is a main challenge for precision medicine. Classical gene-based approaches ignore the modular nature of most human traits, whereas conventional pathway enrichment approaches produce only illustrative results of limited practical utility. Recently, a family of new methods has emerged that change the focus from the whole pathways to the definition of elementary subpathways within them that have any mechanistic significance and to the study of their activities. Thus, mechanistic pathway activity (MPA) methods constitute a new paradigm that allows recoding poorly informative genomic measurements into cell activity quantitative values and relate them to phenotypes. Here we provide a review on the MPA methods available and explain their contribution to systems medicine approaches for addressing challenges in the diagnostic and treatment of complex diseases.
Keywords: Algorithms; Humans; Postmortem Changes; Signal Transduction; Systems biology; Transcriptome

Differential metabolic activity and discovery of therapeutic targets using summarized metabolic pathway models. - Cubuk, Cankut; Hidalgo, Marta R; Amadoz, Alicia; Rian, Kinza; Salavert, Francisco; Pujana, Miguel A; Mateo, Francesca; Herranz, Carmen; Carbonell-Caballero, José; Dopazo, Joaquin (NPJ Syst Biol Appl, 2019)
In spite of the increasing availability of genomic and transcriptomic data, there is still a gap between the detection of perturbations in gene expression and the understanding of their contribution to the molecular mechanisms that ultimately account for the phenotype studied. Alterations in the metabolism are behind the initiation and progression of many diseases, including cancer. The wealth of available knowledge on metabolic processes can therefore be used to derive mechanistic models that link gene expression perturbations to changes in metabolic activity that provide relevant clues on molecular mechanisms of disease and drug modes of action (MoA). In particular, pathway modules, which recapitulate the main aspects of metabolism, are especially suitable for this type of modeling. We present Metabolizer, a web-based application that offers an intuitive, easy-to-use interactive interface to analyze differences in pathway metabolic module activities that can also be used for class prediction and in silico prediction of knock-out (KO) effects. Moreover, Metabolizer can automatically predict the optimal KO intervention for restoring a diseased phenotype. We provide different types of validations of some of the predictions made by Metabolizer. Metabolizer is a web tool that allows understanding molecular mechanisms of disease or the MoA of drugs within the context of the metabolism by using gene expression measurements. In addition, this tool automatically suggests potential therapeutic targets for individualized therapeutic interventions.
Keywords: Computational Biology; Computer Simulation; Drug discovery; Gene Regulatory Networks; Humans; Internet; Metabolic Networks and Pathways; Models, Biological; Neoplasms; Phenotype; Software; Transcriptome

Exploring the druggable space around the Fanconi anemia pathway using machine learning and mechanistic models. - Esteban-Medina, Marina; Peña-Chilet, Maria; Loucera, Carlos; Dopazo, Joaquin (BMC Bioinformatics, 2019)
BACKGROUND: In spite of the abundance of genomic data, predictive models that describe phenotypes as a function of gene expression or mutations are difficult to obtain because they are affected by the curse of dimensionality, given the disbalance between samples and candidate genes. And this is especially dramatic in scenarios in which the availability of samples is difficult, such as the case of rare diseases. RESULTS: The application of multi-output regression machine learning methodologies to predict the potential effect of external proteins over the signaling circuits that trigger Fanconi anemia related cell functionalities, inferred with a mechanistic model, allowed us to detect over 20 potential therapeutic targets. CONCLUSIONS: The use of artificial intelligence methods for the prediction of potentially causal relationships between proteins of interest and cell activities related with disease-related phenotypes opens promising avenues for the systematic search of new targets in rare diseases.
Keywords: Databases, Factual; Fanconi Anemia; Genomics; Humans; Machine Learning; Phenotype; Proteins; Signal Transduction

Pazopanib for treatment of advanced malignant and dedifferentiated solitary fibrous tumour: a multicentre, single-arm, phase 2 trial. - Martin-Broto, Javier; Stacchiotti, Silvia; Lopez-Pousa, Antonio; Redondo, Andres; Bernabeu, Daniel; de Alava, Enrique; Casali, Paolo G; Italiano, Antoine; Gutierrez, Antonio; Moura, David S; Peña-Chilet, Maria; Diaz-Martin, Juan; et al. (Lancet Oncol, 2019)
BACKGROUND: A solitary fibrous tumour is a rare soft-tissue tumour with three clinicopathological variants: typical, malignant, and dedifferentiated. Preclinical experiments and retrospective studies have shown different sensitivities of solitary fibrous tumour to chemotherapy and antiangiogenics. We therefore designed a trial to assess the activity of pazopanib in a cohort of patients with malignant or dedifferentiated solitary fibrous tumour. The clinical and translational results are presented here. METHODS: In this single-arm, phase 2 trial, adult patients (aged ≥ 18 years) with histologically confirmed metastatic or unresectable malignant or dedifferentiated solitary fibrous tumour at any location, who had progressed (by RECIST and Choi criteria) in the previous 6 months and had an ECOG performance status of 0-2, were enrolled at 16 third-level hospitals with expertise in sarcoma care in Spain, Italy, and France. Patients received pazopanib 800 mg once daily, taken orally without food, at least 1 h before or 2 h after a meal, until progression or intolerance. The primary endpoint of the study was overall response measured by Choi criteria in the subset of the intention-to-treat population (patients who received at least 1 month of treatment with at least one radiological assessment). All patients who received at least one dose of the study drug were included in the safety analyses. This study is registered with ClinicalTrials.gov, number NCT02066285, and with the European Clinical Trials Database, EudraCT number 2013-005456-15. FINDINGS: From June 26, 2014, to Nov 24, 2016, of 40 patients assessed, 36 were enrolled (34 with malignant solitary fibrous tumour and two with dedifferentiated solitary fibrous tumour). Median follow-up was 27 months (IQR 16-31). Based on central radiology review, 18 (51%) of 35 evaluable patients had partial responses, nine (26%) had stable disease, and eight (23%) had progressive disease according to Choi criteria. Further enrolment of patients with dedifferentiated solitary fibrous tumour was stopped after detection of early and fast progressions in a planned interim analysis. 51% (95% CI 34-69) of 35 patients achieved an overall response according to Choi criteria. Ten (29%) of 35 patients died. There were no deaths related to adverse events and the most frequent grade 3 or higher adverse events were hypertension (11 [31%] of 36 patients), neutropenia (four [11%]), increased concentrations of alanine aminotransferase (four [11%]), and increased concentrations of bilirubin (three [8%]). INTERPRETATION: To our knowledge, this is the first trial of pazopanib for treatment of malignant solitary fibrous tumour showing activity in this patient group. The manageable toxicity profile and the activity shown by pazopanib suggests that this drug could be an option for systemic treatment of advanced malignant solitary fibrous tumour, and provides a benchmark for future trials. FUNDING: Spanish Group for Research on Sarcomas (GEIS), Italian Sarcoma Group (ISG), French Sarcoma Group (FSG), GlaxoSmithKline, and Novartis.
Keywords: Adult; Aged; Angiogenesis Inhibitors; Antineoplastic Agents; Female; Humans; Indazoles; Male; Middle Aged; Multivariate Analysis; Pyrimidines; Response Evaluation Criteria in Solid Tumors; Soft Tissue Neoplasms; Solitary Fibrous Tumors; Sulfonamides; Survival Analysis

Precision medicine needs pioneering clinical bioinformaticians. - Gómez-López, Gonzalo; Dopazo, Joaquin; Cigudosa, Juan C; Valencia, Alfonso; Al-Shahrour, Fátima (Brief Bioinform, 2019)
Success in precision medicine depends on accessing high-quality genetic and molecular data from large, well-annotated patient cohorts that couple biological samples to comprehensive clinical data, which in conjunction can lead to effective therapies. From such a scenario emerges the need for a new professional profile, an expert bioinformatician with training in clinical areas who can make sense of multi-omics data to improve therapeutic interventions in patients, and the design of optimized basket trials. In this review, we first describe the main policies and international initiatives that focus on precision medicine. Secondly, we review the currently ongoing clinical trials in precision medicine, introducing the concept of 'precision bioinformatics', and we describe current pioneering bioinformatics efforts aimed at implementing tools and computational infrastructures for precision medicine in health institutions around the world. Thirdly, we discuss the challenges related to the clinical training of bioinformaticians, and the urgent need for computational specialists capable of assimilating medical terminologies and protocols to address real clinical questions. We also propose some skills required to carry out common tasks in clinical bioinformatics and some tips for emergent groups. Finally, we explore the future perspectives and the challenges faced by precision medicine bioinformatics.
Keywords: Cohort Studies; Computational Biology; Humans; Precision Medicine

The effects of death and post-mortem cold ischemia on human tissue transcriptomes. - Ferreira, Pedro G; Muñoz-Aguirre, Manuel; Reverter, Ferran; Sá Godinho, Caio P; Sousa, Abel; Amadoz, Alicia; Sodaei, Reza; Hidalgo, Marta R; Pervouchine, Dmitri; Carbonell-Caballero, José; Nurtdinov, Ramil; Breschi, Alessandra; et al. (Nat Commun, 2018)
Post-mortem tissues samples are a key resource for investigating patterns of gene expression. However, the processes triggered by death and the post-mortem interval (PMI) can significantly alter physiologically normal RNA levels. We investigate the impact of PMI on gene expression using data from multiple tissues of post-mortem donors obtained from the GTEx project. We find that many genes change expression over relatively short PMIs in a tissue-specific manner, but this potentially confounding effect in a biological analysis can be minimized by taking into account appropriate covariates. By comparing ante- and post-mortem blood samples, we identify the cascade of transcriptional events triggered by death of the organism. These events do not appear to simply reflect stochastic variation resulting from mRNA degradation, but active and ongoing regulation of transcription. Finally, we develop a model to predict the time since death from the analysis of the transcriptome of a few readily accessible tissues.
Keywords: Blood; Cold Ischemia; Death; Female; gene expression; Humans; Models, Biological; Postmortem Changes; RNA, Messenger; Stochastic Processes; Transcriptome

The first complete genomic structure of Butyrivibrio fibrisolvens and its chromid. - Rodríguez Hernáez, Javier; Cerón Cucchi, Maria Esperanza; Cravero, Silvio; Martinez, Maria Carolina; Gonzalez, Sergio; Puebla, Andrea; Dopazo, Joaquin; Farber, Marisa; Paniego, Norma; Rivarola, Máximo (Microb Genom, 2018)
Butyrivibrio fibrisolvens forms part of the gastrointestinal microbiome of ruminants and other mammals, including humans. Indeed, it is one of the most common bacteria found in the rumen and plays an important role in ruminal fermentation of polysaccharides, yet, to date, there is no closed reference genome published for this species in any ruminant animal. We successfully assembled the nearly complete genome sequence of B. fibrisolvens strain INBov1 isolated from cow rumen using Illumina paired-end reads, 454 Roche single-end and mate pair sequencing technology. Additionally, we constructed an optical restriction map of this strain to aid in scaffold ordering and positioning, and completed the first genomic structure of this species. Moreover, we identified and assembled the first chromid of this species (pINBov266). The INBov1 genome encodes a large set of genes involved in the cellulolytic process but lacks key genes. This seems to indicate that B. fibrisolvens plays an important role in ruminal cellulolytic processes, but does not have autonomous cellulolytic capacity. When searching for genes involved in the biohydrogenation of unsaturated fatty acids, no linoleate isomerase gene was found in this strain. INBov1 does encode oleate hydratase genes known to participate in the hydrogenation of oleic acids. Furthermore, INBov1 contains an enolase gene, which has been recently determined to participate in the synthesis of conjugated linoleic acids. This work confirms the presence of a novel chromid in B. fibrisolvens and provides a new potential reference genome sequence for this species, providing new insight into its role in biohydrogenation and carbohydrate degradation.
Keywords: Animals; Butyrivibrio fibrisolvens; Cattle; Genome, Bacterial; Genomics; Humans; Milk; Rumen; Sequence Analysis, DNA

Gene Expression Integration into Pathway Modules Reveals a Pan-Cancer Metabolic Landscape. - Cubuk, Cankut; Hidalgo, Marta R; Amadoz, Alicia; Pujana, Miguel A; Mateo, Francesca; Herranz, Carmen; Carbonell-Caballero, José; Dopazo, Joaquin (Cancer Res, 2018)
Metabolic reprogramming plays an important role in cancer development and progression and is a well-established hallmark of cancer. Despite its inherent complexity, cellular metabolism can be decomposed into functional modules that represent fundamental metabolic processes. Here, we performed a pan-cancer study involving 9,428 samples from 25 cancer types to reveal metabolic modules whose individual or coordinated activity predict cancer type and outcome, in turn highlighting novel therapeutic opportunities. Integration of gene expression levels into metabolic modules suggests that the activity of specific modules differs between cancers and the corresponding tissues of origin. Some modules may cooperate, as indicated by the positive correlation of their activity across a range of tumors. The activity of many metabolic modules was significantly associated with prognosis at a stronger magnitude than any of their constituent genes. Thus, modules may be classified as tumor suppressors and oncomodules according to their potential impact on cancer progression. Using this modeling framework, we also propose novel potential therapeutic targets that constitute alternative ways of treating cancer by inhibiting their reprogrammed metabolism. Collectively, this study provides an extensive resource of predicted cancer metabolic profiles and dependencies. Combining gene expression with metabolic modules identifies molecular mechanisms of cancer undetected on an individual gene level and allows discovery of new potential therapeutic targets. .
Keywords: Cell Line, Tumor; Cluster Analysis; Disease Progression; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Humans; Kaplan-Meier Estimate; Metabolome; mutation; Neoplasms; Oncogenes; Phenotype; Prognosis; RNA, Small Interfering; Sequence Analysis, RNA; Transcriptome; Treatment Outcome

Models of cell signaling uncover molecular mechanisms of high-risk neuroblastoma and predict disease outcome. - Hidalgo, Marta R; Amadoz, Alicia; Cubuk, Cankut; Carbonell-Caballero, José; Dopazo, Joaquin (Biol Direct, 2018)
BACKGROUND: Despite the progress in neuroblastoma therapies the mortality of high-risk patients is still high (40-50%) and the molecular basis of the disease remains poorly known. Recently, a mathematical model was used to demonstrate that the network regulating stress signaling by the c-Jun N-terminal kinase pathway played a crucial role in survival of patients with neuroblastoma irrespective of their MYCN amplification status. This demonstrates the enormous potential of computational models of biological modules for the discovery of underlying molecular mechanisms of diseases. RESULTS: Since signaling is known to be highly relevant in cancer, we have used a computational model of the whole cell signaling network to understand the molecular determinants of bad prognostic in neuroblastoma. Our model produced a comprehensive view of the molecular mechanisms of neuroblastoma tumorigenesis and progression. CONCLUSION: We have also shown how the activity of signaling circuits can be considered a reliable model-based prognostic biomarker. REVIEWERS: This article was reviewed by Tim Beissbarth, Wenzhong Xiao and Joanna Polanska. For the full reviews, please go to the Reviewers' comments section.
Keywords: Computational Biology; Gene Expression Regulation, Neoplastic; Humans; JNK Mitogen-Activated Protein Kinases; Models, Theoretical; Neuroblastoma; Signal Transduction

The modular network structure of the mutational landscape of Acute Myeloid Leukemia. - Ibáñez, Mariam; Carbonell-Caballero, José; Such, Esperanza; García-Alonso, Luz; Liquori, Alessandro; López-Pavía, María; LLop, Marta; Alonso, Carmen; Barragán, Eva; Gómez-Seguí, Inés; Neef, Alexander; Hervás, David; et al. (PLoS One, 2018)
Acute myeloid leukemia (AML) is associated with the sequential accumulation of acquired genetic alterations. Although at diagnosis cytogenetic alterations are frequent in AML, roughly 50% of patients present an apparently normal karyotype (NK), leading to a highly heterogeneous prognosis. Due to this significant heterogeneity, it has been suggested that different molecular mechanisms may trigger the disease with diverse prognostic implications. We performed whole-exome sequencing (WES) of tumor-normal matched samples of de novo AML-NK patients lacking mutations in NPM1, CEBPA or FLT3-ITD to identify new gene mutations with potential prognostic and therapeutic relevance to patients with AML. Novel candidate-genes, together with others previously described, were targeted resequenced in an independent cohort of 100 de novo AML patients classified in the cytogenetic intermediate-risk (IR) category. A mean of 4.89 mutations per sample were detected in 73 genes, 35 of which were mutated in more than one patient. After a network enrichment analysis, we defined a single in silico model and established a set of seed-genes that may trigger leukemogenesis in patients with normal karyotype. The high heterogeneity of gene mutations observed in AML patients suggested that a specific alteration could not be as essential as the interaction of deregulated pathways.
Keywords: Adult; Aged; Cytodiagnosis; Exome Sequencing; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Heterogeneity; Humans; Karyotype; Leukemia, Myeloid, Acute; Male; Middle Aged; mutation; Neoplasm Proteins; Nucleophosmin; Prognosis

Genomic expression differences between cutaneous cells from red hair color individuals and black hair color individuals based on bioinformatic analysis. - Puig-Butille, Joan Anton; Gimenez-Xavier, Pol; Visconti, Alessia; Nsengimana, Jérémie; Garcia-Garcia, Francisco; Tell-Marti, Gemma; Escamez, Maria José; Newton-Bishop, Julia; Bataille, Veronique; Del Rio, Marcela; Dopazo, Joaquin; Falchi, Mario; et al. (Oncotarget, 2017)
The MC1R gene plays a crucial role in pigmentation synthesis. Loss-of-function MC1R variants, which impair protein function, are associated with red hair color (RHC) phenotype and increased skin cancer risk. Cultured cutaneous cells bearing loss-of-function MC1R variants show a distinct gene expression profile compared to wild-type MC1R cultured cutaneous cells. We analysed the gene signature associated with RHC co-cultured melanocytes and keratinocytes by Protein-Protein interaction (PPI) network analysis to identify genes related with non-functional MC1R variants. From two detected networks, we selected 23 nodes as hub genes based on topological parameters. Differential expression of hub genes was then evaluated in healthy skin biopsies from RHC and black hair color (BHC) individuals. We also compared gene expression in melanoma tumors from individuals with RHC versus BHC. Gene expression in normal skin from RHC cutaneous cells showed dysregulation in 8 out of 23 hub genes (CLN3, ATG10, WIPI2, SNX2, GABARAPL2, YWHA, PCNA and GBAS). Hub genes did not differ between melanoma tumors in RHC versus BHC individuals. The study suggests that healthy skin cells from RHC individuals present a constitutive genomic deregulation associated with the red hair phenotype and identify novel genes involved in melanocyte biology.
Keywords: Adult; Coculture Techniques; Computational Biology; gene expression; Genetic Predisposition to Disease; Genomics; Hair Color; Humans; Keratinocytes; Melanocytes; Middle Aged; Phenotype; Receptor, Melanocortin, Type 1

GGPS1 Mutation and Atypical Femoral Fractures with Bisphosphonates. - Roca-Ayats, Neus; Balcells, Susana; Garcia-Giralt, Natàlia; Falcó-Mascaró, Maite; Martínez-Gil, Núria; Abril, Josep F; Urreizti, Roser; Dopazo, Joaquin; Quesada-Gómez, José M; Nogués, Xavier; Mellibovsky, Leonardo; Prieto-Alhambra, Daniel; et al. (N Engl J Med, 2017)
Keywords: Aged; Amino Acid Sequence; Bone Density Conservation Agents; Dimethylallyltranstransferase; Diphosphonates; Exome; Farnesyltranstransferase; Female; Femoral Fractures; Geranyltranstransferase; Humans; Middle Aged; mutation

Graph-theoretical comparison of normal and tumor networks in identifying BRCA genes. - Dopazo, Joaquin; Erten, Cesim (BMC Syst Biol, 2017)
BACKGROUND: Identification of driver genes related to certain types of cancer is an important research topic. Several systems biology approaches have been suggested, in particular for the identification of breast cancer (BRCA) related genes. Such approaches usually rely on differential gene expression and/or mutational landscape data. In some cases interaction network data is also integrated to identify cancer-related modules computationally. RESULTS: We provide a framework for the comparative graph-theoretical analysis of networks integrating the relevant gene expression, mutations, and potein-protein interaction network data. The comparisons involve a graph-theoretical analysis of normal and tumor network pairs across all instances of a given set of breast cancer samples. The network measures under consideration are based on appropriate formulations of various centrality measures: betweenness, clustering coefficients, degree centrality, random walk distances, graph-theoretical distances, and Jaccard index centrality. CONCLUSIONS: Among all the studied centrality-based graph-theoretical properties, we show that a betweenness-based measure differentiates BRCA genes across all normal versus tumor network pairs, than the rest of the popular centrality-based measures. The AUROC and AUPR values of the gene lists ordered with respect to the measures under study as compared to NCBI BioSystems pathway and the COSMIC database of cancer genes are the largest with the betweenness-based differentiation, followed by the measure based on degree centrality. In order to test the robustness of the suggested measures in prioritizing cancer genes, we further tested the two most promising measures, those based on betweenness and degree centralities, on randomly rewired networks. We show that both measures are quite resilient to noise in the input interaction network. We also compared the same measures against a state-of-the-art alternative disease gene prioritization method, MUFFFINN. We show that both our graph-theoretical measures outperform MUFFINN prioritizations in terms of ROC and precions/recall analysis. Finally, we filter the ordered list of the best measure, the betweenness-based differentiation, via a maximum-weight independent set formulation and investigate the top 50 genes in regards to literature verification. We show that almost all genes in the list are verified by the breast cancer literature and three genes are presented as novel genes that may potentialy be BRCA-related but missing in literature.
Keywords: Breast Neoplasms; Female; Gene Regulatory Networks; Genes, Tumor Suppressor; Humans; Models, Theoretical; mutation

HGVA: the Human Genome Variation Archive. - Lopez, Javier; Coll, Jacobo; Haimel, Matthias; Kandasamy, Swaathi; Tárraga, Joaquín; Furio-Tari, Pedro; Bari, Wasim; Bleda, Marta; Rueda, Antonio; Gräf, Stefan; Rendon, Augusto; Dopazo, Joaquin; et al. (Nucleic Acids Res, 2017)
High-profile genomic variation projects like the 1000 Genomes project or the Exome Aggregation Consortium, are generating a wealth of human genomic variation knowledge which can be used as an essential reference for identifying disease-causing genotypes. However, accessing these data, contrasting the various studies and integrating those data in downstream analyses remains cumbersome. The Human Genome Variation Archive (HGVA) tackles these challenges and facilitates access to genomic data for key reference projects in a clean, fast and integrated fashion. HGVA provides an efficient and intuitive web-interface for easy data mining, a comprehensive RESTful API and client libraries in Python, Java and JavaScript for fast programmatic access to its knowledge base. HGVA calculates population frequencies for these projects and enriches their data with variant annotation provided by CellBase, a rich and fast annotation solution. HGVA serves as a proof-of-concept of the genome analysis developments being carried out by the University of Cambridge together with UK's 100 000 genomes project and the National Institute for Health Research BioResource Rare-Diseases, in particular, deploying open-source for Computational Biology (OpenCB) software platform for storing and analyzing massive genomic datasets.
Keywords: Genetic Variation; Genome, Human; Humans; Internet; Software; User-Computer Interface

High throughput estimation of functional cell activities reveals disease mechanisms and predicts relevant clinical outcomes. - Hidalgo, Marta R; Cubuk, Cankut; Amadoz, Alicia; Salavert, Francisco; Carbonell-Caballero, José; Dopazo, Joaquin (Oncotarget, 2017)
Understanding the aspects of the cell functionality that account for disease or drug action mechanisms is a main challenge for precision medicine. Here we propose a new method that models cell signaling using biological knowledge on signal transduction. The method recodes individual gene expression values (and/or gene mutations) into accurate measurements of changes in the activity of signaling circuits, which ultimately constitute high-throughput estimations of cell functionalities caused by gene activity within the pathway. Moreover, such estimations can be obtained either at cohort-level, in case/control comparisons, or personalized for individual patients. The accuracy of the method is demonstrated in an extensive analysis involving 5640 patients from 12 different cancer types. Circuit activity measurements not only have a high diagnostic value but also can be related to relevant disease outcomes such as survival, and can be used to assess therapeutic interventions.
Keywords: Computational Biology; gene expression; Gene Regulatory Networks; Humans; mutation; Neoplasms; Precision Medicine; Sequence Analysis, RNA; Signal Transduction

Mutations in TRAPPC11 are associated with a congenital disorder of glycosylation. - Matalonga, Leslie; Bravo, Miren; Serra-Peinado, Carla; García-Pelegrí, Elisabeth; Ugarteburu, Olatz; Vidal, Silvia; Llambrich, Maria; Quintana, Ester; Fuster-Jorge, Pedro; Gonzalez-Bravo, Maria Nieves; Beltran, Sergi; Dopazo, Joaquin; et al. (Hum Mutat, 2017)
Congenital disorders of glycosylation (CDG) are a heterogeneous and rapidly growing group of diseases caused by abnormal glycosylation of proteins and/or lipids. Mutations in genes involved in the homeostasis of the endoplasmic reticulum (ER), the Golgi apparatus (GA), and the vesicular trafficking from the ER to the ER-Golgi intermediate compartment (ERGIC) have been found to be associated with CDG. Here, we report a patient with defects in both N- and O-glycosylation combined with a delayed vesicular transport in the GA due to mutations in TRAPPC11, a subunit of the TRAPPIII complex. TRAPPIII is implicated in the anterograde transport from the ER to the ERGIC as well as in the vesicle export from the GA. This report expands the spectrum of genetic alterations associated with CDG, providing new insights for the diagnosis and the understanding of the physiopathological mechanisms underlying glycosylation disorders.
Keywords: Abnormalities, Multiple; Alleles; Amino Acid Substitution; Brain; Congenital Disorders of Glycosylation; Genotype; Humans; Magnetic Resonance Imaging; Male; mutation; Phenotype; Vesicular Transport Proteins; Whole Genome Sequencing

Reference genome assessment from a population scale perspective: an accurate profile of variability and noise. - Carbonell-Caballero, José; Amadoz, Alicia; Alonso, Roberto; Hidalgo, Marta R; Cubuk, Cankut; Conesa, David; López-Quílez, Antonio; Dopazo, Joaquin (Bioinformatics, 2017)
MOTIVATION: Current plant and animal genomic studies are often based on newly assembled genomes that have not been properly consolidated. In this scenario, misassembled regions can easily lead to false-positive findings. Despite quality control scores are included within genotyping protocols, they are usually employed to evaluate individual sample quality rather than reference sequence reliability. We propose a statistical model that combines quality control scores across samples in order to detect incongruent patterns at every genomic region. Our model is inherently robust since common artifact signals are expected to be shared between independent samples over misassembled regions of the genome. RESULTS: The reliability of our protocol has been extensively tested through different experiments and organisms with accurate results, improving state-of-the-art methods. Our analysis demonstrates synergistic relations between quality control scores and allelic variability estimators, that improve the detection of misassembled regions, and is able to find strong artifact signals even within the human reference assembly. Furthermore, we demonstrated how our model can be trained to properly rank the confidence of a set of candidate variants obtained from new independent samples. AVAILABILITY AND IMPLEMENTATION: This tool is freely available at http://gitlab.com/carbonell/ces. CONTACT: jcarbonell.cipf@gmail.com or joaquin.dopazo@juntadeandalucia.es. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Animals; Genetic Variation; Genome; Genomics; Genotype; Humans; Models, Statistical; Quality Control; Reproducibility of Results; Software

VISMapper: ultra-fast exhaustive cartography of viral insertion sites for gene therapy. - Juanes, José M; Gallego, Asunción; Tárraga, Joaquín; Chaves, Felipe J; Marin-Garcia, Pablo; Medina, Ignacio; Arnau, Vicente; Dopazo, Joaquin (BMC Bioinformatics, 2017)
BACKGROUND: The possibility of integrating viral vectors to become a persistent part of the host genome makes them a crucial element of clinical gene therapy. However, viral integration has associated risks, such as the unintentional activation of oncogenes that can result in cancer. Therefore, the analysis of integration sites of retroviral vectors is a crucial step in developing safer vectors for therapeutic use. RESULTS: Here we present VISMapper, a vector integration site analysis web server, to analyze next-generation sequencing data for retroviral vector integration sites. VISMapper can be found at: http://vismapper.babelomics.org . CONCLUSIONS: Because it uses novel mapping algorithms VISMapper is remarkably faster than previous available programs. It also provides a useful graphical interface to analyze the integration sites found in the genomic context.
Keywords: Base Sequence; Genetic Therapy; Genetic Vectors; High-Throughput Nucleotide Sequencing; Humans; Internet; User-Computer Interface; Virus Integration

Improving the management of Inherited Retinal Dystrophies by targeted sequencing of a population-specific gene panel. - Bravo-Gil, Nereida; Méndez-Vidal, Cristina; Romero-Pérez, Laura; González-del Pozo, María; Rodríguez-de la Rúa, Enrique; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (Sci Rep, 2016)
Next-generation sequencing (NGS) has overcome important limitations to the molecular diagnosis of Inherited Retinal Dystrophies (IRD) such as the high clinical and genetic heterogeneity and the overlapping phenotypes. The purpose of this study was the identification of the genetic defect in 32 Spanish families with different forms of IRD. With that aim, we implemented a custom NGS panel comprising 64 IRD-associated genes in our population, and three disease-associated intronic regions. A total of 37 pathogenic mutations (14 novels) were found in 73% of IRD patients ranging from 50% for autosomal dominant cases, 75% for syndromic cases, 83% for autosomal recessive cases, and 100% for X-linked cases. Additionally, unexpected phenotype-genotype correlations were found in 6 probands, which led to the refinement of their clinical diagnoses. Furthermore, intra- and interfamilial phenotypic variability was observed in two cases. Moreover, two cases unsuccessfully analysed by exome sequencing were resolved by applying this panel. Our results demonstrate that this hypothesis-free approach based on frequently mutated, population-specific loci is highly cost-efficient for the routine diagnosis of this heterogeneous condition and allows the unbiased analysis of a miscellaneous cohort. The molecular information found here has aid clinical diagnosis and has improved genetic counselling and patient management.
Keywords: Alleles; Computer Simulation; DNA Copy Number Variations; DNA Mutational Analysis; Eye Proteins; Gene Library; Genetic Association Studies; Genetic Heterogeneity; Genetic Therapy; High-Throughput Nucleotide Sequencing; Humans; mutation; Phenotype; Retinal Dystrophies

Integrated gene set analysis for microRNA studies. - Garcia-Garcia, Francisco; Panadero, Joaquin; Dopazo, Joaquin; Montaner, David (Bioinformatics, 2016)
MOTIVATION: Functional interpretation of miRNA expression data is currently done in a three step procedure: select differentially expressed miRNAs, find their target genes, and carry out gene set overrepresentation analysis Nevertheless, major limitations of this approach have already been described at the gene level, while some newer arise in the miRNA scenario.Here, we propose an enhanced methodology that builds on the well-established gene set analysis paradigm. Evidence for differential expression at the miRNA level is transferred to a gene differential inhibition score which is easily interpretable in terms of gene sets or pathways. Such transferred indexes account for the additive effect of several miRNAs targeting the same gene, and also incorporate cancellation effects between cases and controls. Together, these two desirable characteristics allow for more accurate modeling of regulatory processes. RESULTS: We analyze high-throughput sequencing data from 20 different cancer types and provide exhaustive reports of gene and Gene Ontology-term deregulation by miRNA action. AVAILABILITY AND IMPLEMENTATION: The proposed methodology was implemented in the Bioconductor library mdgsa http://bioconductor.org/packages/mdgsa For the purpose of reproducibility all of the scripts are available at https://github.com/dmontaner-papers/gsa4mirna CONTACT: : david.montaner@gmail.com SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computational Biology; Gene Expression Profiling; Gene ontology; Gene Regulatory Networks; High-Throughput Nucleotide Sequencing; Humans; MicroRNAs; Neoplasms; Reproducibility of Results

The Mutational Landscape of Acute Promyelocytic Leukemia Reveals an Interacting Network of Co-Occurrences and Recurrent Mutations. - Ibáñez, Mariam; Carbonell-Caballero, José; García-Alonso, Luz; Such, Esperanza; Jiménez-Almazán, Jorge; Vidal, Enrique; Barragán, Eva; López-Pavía, María; LLop, Marta; Martín, Iván; Gómez-Seguí, Inés; Montesinos, Pau; et al. (PLoS One, 2016)
Preliminary Acute Promyelocytic Leukemia (APL) whole exome sequencing (WES) studies have identified a huge number of somatic mutations affecting more than a hundred different genes mainly in a non-recurrent manner, suggesting that APL is a heterogeneous disease with secondary relevant changes not yet defined. To extend our knowledge of subtle genetic alterations involved in APL that might cooperate with PML/RARA in the leukemogenic process, we performed a comprehensive analysis of somatic mutations in APL combining WES with sequencing of a custom panel of targeted genes by next-generation sequencing. To select a reduced subset of high confidence candidate driver genes, further in silico analysis were carried out. After prioritization and network analysis we found recurrent deleterious mutations in 8 individual genes (STAG2, U2AF1, SMC1A, USP9X, IKZF1, LYN, MYCBP2 and PTPN11) with a strong potential of being involved in APL pathogenesis. Our network analysis of multiple mutations provides a reliable approach to prioritize genes for additional analysis, improving our knowledge of the leukemogenesis interactome. Additionally, we have defined a functional module in the interactome of APL. The hypothesis is that the number, or the specific combinations, of mutations harbored in each patient might not be as important as the disturbance caused in biological key functions, triggered by several not necessarily recurrent mutations.
Keywords: Exome; Gene Regulatory Networks; Genome, Human; Humans; INDEL Mutation; Leukemia, Promyelocytic, Acute; mutation; Mutation Rate; Polymorphism, Single Nucleotide; Reproducibility of Results

Mutations in the MORC2 gene cause axonal Charcot-Marie-Tooth disease. - Sevilla, Teresa; Lupo, Vincenzo; Martínez-Rubio, Dolores; Sancho, Paula; Sivera, Rafael; Chumillas, María J; García-Romero, Mar; Pascual-Pascual, Samuel I; Muelas, Nuria; Dopazo, Joaquin; Vílchez, Juan J; Palau, Francesc; et al. (Brain, 2016)
Charcot-Marie-Tooth disease (CMT) is a complex disorder with wide genetic heterogeneity. Here we present a new axonal Charcot-Marie-Tooth disease form, associated with the gene microrchidia family CW-type zinc finger 2 (MORC2). Whole-exome sequencing in a family with autosomal dominant segregation identified the novel MORC2 p.R190W change in four patients. Further mutational screening in our axonal Charcot-Marie-Tooth disease clinical series detected two additional sporadic cases, one patient who also carried the same MORC2 p.R190W mutation and another patient that harboured a MORC2 p.S25L mutation. Genetic and in silico studies strongly supported the pathogenicity of these sequence variants. The phenotype was variable and included patients with congenital or infantile onset, as well as others whose symptoms started in the second decade. The patients with early onset developed a spinal muscular atrophy-like picture, whereas in the later onset cases, the initial symptoms were cramps, distal weakness and sensory impairment. Weakness and atrophy progressed in a random and asymmetric fashion and involved limb girdle muscles, leading to a severe incapacity in adulthood. Sensory loss was always prominent and proportional to disease severity. Electrophysiological studies were consistent with an asymmetric axonal motor and sensory neuropathy, while fasciculations and myokymia were recorded rather frequently by needle electromyography. Sural nerve biopsy revealed pronounced multifocal depletion of myelinated fibres with some regenerative clusters and occasional small onion bulbs. Morc2 is expressed in both axons and Schwann cells of mouse peripheral nerve. Different roles in biological processes have been described for MORC2. As the silencing of Charcot-Marie-Tooth disease genes have been associated with DNA damage response, it is tempting to speculate that a deregulation of this pathway may be linked to the axonal degeneration observed in MORC2 neuropathy, thus adding a new pathogenic mechanism to the long list of causes of Charcot-Marie-Tooth disease.
Keywords: Adult; Aged; Animals; Axons; Charcot-Marie-Tooth Disease; Female; gene expression; Humans; Infant; Male; Mice; Middle Aged; mutation; Pedigree; Phenotype; Sciatic Nerve; Sural Nerve; Transcription Factors; Young Adult

Progress in pharmacogenetics: consortiums and new strategies. - Maroñas, Olalla; Latorre, Ana; Dopazo, Joaquin; Pirmohamed, Munir; Rodríguez-Antona, Cristina; Siest, Gérard; Carracedo, Ángel; LLerena, Adrián (Drug Metab Pers Ther, 2016)
Pharmacogenetics (PGx), as a field dedicated to achieving the goal of personalized medicine (PM), is devoted to the study of genes involved in inter-individual response to drugs. Due to its nature, PGx requires access to large samples; therefore, in order to progress, the formation of collaborative consortia seems to be crucial. Some examples of this collective effort are the European Society of Pharmacogenomics and personalized Therapy and the Ibero-American network of Pharmacogenetics. As an emerging field, one of the major challenges that PGx faces is translating their discoveries from research bench to bedside. The development of genomic high-throughput technologies is generating a revolution and offers the possibility of producing vast amounts of genome-wide single nucleotide polymorphisms for each patient. Moreover, there is a need of identifying and replicating associations of new biomarkers, and, in addition, a greater effort must be invested in developing regulatory organizations to accomplish a correct standardization. In this review, we outline the current progress in PGx using examples to highlight both the importance of polymorphisms and the research strategies for their detection. These concepts need to be applied together with a proper dissemination of knowledge to improve clinician and patient understanding, in a multidisciplinary team-based approach.
Keywords: Cooperative Behavior; Genome-Wide Association Study; High-Throughput Screening Assays; Humans; Patient Care Team; pharmacogenetics; Polymorphism, Single Nucleotide; Precision Medicine

Screening of CD96 and ASXL1 in 11 patients with Opitz C or Bohring-Opitz syndromes. - Urreizti, Roser; Roca-Ayats, Neus; Trepat, Judith; Garcia-Garcia, Francisco; Alemán, Alejandro; Orteschi, Daniela; Marangi, Giuseppe; Neri, Giovanni; Opitz, John M; Dopazo, Joaquin; Cormand, Bru; Vilageliu, Lluïsa; et al. (Am J Med Genet A, 2016)
Opitz C trigonocephaly (or Opitz C syndrome, OTCS) and Bohring-Opitz syndrome (BOS or C-like syndrome) are two rare genetic disorders with phenotypic overlap. The genetic causes of these diseases are not understood. However, two genes have been associated with OTCS or BOS with dominantly inherited de novo mutations. Whereas CD96 has been related to OTCS (one case) and to BOS (one case), ASXL1 has been related to BOS only (several cases). In this study we analyze CD96 and ASXL1 in a group of 11 affected individuals, including 2 sibs, 10 of them were diagnosed with OTCS, and one had a BOS phenotype. Exome sequences were available on six patients with OTCS and three parent pairs. Thus, we could analyze the CD96 and ASXL1 sequences in these patients bioinformatically. Sanger sequencing of all exons of CD96 and ASXL1 was carried out in the remaining patients. Detailed scrutiny of the sequences and assessment of variants allowed us to exclude putative pathogenic and private mutations in all but one of the patients. In this patient (with BOS) we identified a de novo mutation in ASXL1 (c.2100dupT). By nature and location within the gene, this mutation resembles those previously described in other BOS patients and we conclude that it may be responsible for the condition. Our results indicate that in 10 of 11, the disease (OTCS or BOS) cannot be explained by small changes in CD96 or ASXL1. However, the cohort is too small to make generalizations about the genetic etiology of these diseases.
Keywords: Adolescent; Antigens, CD; Child; Child, Preschool; Craniosynostoses; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Intellectual Disability; Male; mutation; Pedigree; Phenotype; Prognosis; Repressor Proteins

Serum metabolomic profiling facilitates the non-invasive identification of metabolic biomarkers associated with the onset and progression of non-small cell lung cancer. - Puchades-Carrasco, Leonor; Jantus-Lewintre, Eloisa; Pérez-Rambla, Clara; Garcia-Garcia, Francisco; Lucas, Rut; Calabuig, Silvia; Blasco, Ana; Dopazo, Joaquin; Camps, Carlos; Pineda-Lucena, Antonio (Oncotarget, 2016)
Lung cancer (LC) is responsible for most cancer deaths. One of the main factors contributing to the lethality of this disease is the fact that a large proportion of patients are diagnosed at advanced stages when a clinical intervention is unlikely to succeed. In this study, we evaluated the potential of metabolomics by 1H-NMR to facilitate the identification of accurate and reliable biomarkers to support the early diagnosis and prognosis of non-small cell lung cancer (NSCLC).We found that the metabolic profile of NSCLC patients, compared with healthy individuals, is characterized by statistically significant changes in the concentration of 18 metabolites representing different amino acids, organic acids and alcohols, as well as different lipids and molecules involved in lipid metabolism. Furthermore, the analysis of the differences between the metabolic profiles of NSCLC patients at different stages of the disease revealed the existence of 17 metabolites involved in metabolic changes associated with disease progression.Our results underscore the potential of metabolomics profiling to uncover pathophysiological mechanisms that could be useful to objectively discriminate NSCLC patients from healthy individuals, as well as between different stages of the disease.
Keywords: Adult; Aged; Biomarkers, Tumor; Carcinoma, Non-Small-Cell Lung; Disease Progression; Female; Humans; Lung Neoplasms; Male; metabolomics; Middle Aged; Proton Magnetic Resonance Spectroscopy

Whole exome sequencing of Rett syndrome-like patients reveals the mutational diversity of the clinical phenotype. - Lucariello, Mario; Vidal, Enrique; Vidal, Silvia; Saez, Mauricio; Roa, Laura; Huertas, Dori; Pineda, Mercè; Dalfó, Esther; Dopazo, Joaquin; Jurado, Paola; Armstrong, Judith; Esteller, Manel (Hum Genet, 2016)
Classical Rett syndrome (RTT) is a neurodevelopmental disorder where most of cases carry MECP2 mutations. Atypical RTT variants involve mutations in CDKL5 and FOXG1. However, a subset of RTT patients remains that do not carry any mutation in the described genes. Whole exome sequencing was carried out in a cohort of 21 female probands with clinical features overlapping with those of RTT, but without mutations in the customarily studied genes. Candidates were functionally validated by assessing the appearance of a neurological phenotype in Caenorhabditis elegans upon disruption of the corresponding ortholog gene. We detected pathogenic variants that accounted for the RTT-like phenotype in 14 (66.6 %) patients. Five patients were carriers of mutations in genes already known to be associated with other syndromic neurodevelopmental disorders. We determined that the other patients harbored mutations in genes that have not previously been linked to RTT or other neurodevelopmental syndromes, such as the ankyrin repeat containing protein ANKRD31 or the neuronal acetylcholine receptor subunit alpha-5 (CHRNA5). Furthermore, worm assays demonstrated that mutations in the studied candidate genes caused locomotion defects. Our findings indicate that mutations in a variety of genes contribute to the development of RTT-like phenotypes.
Keywords: Adolescent; Adult; Animals; Caenorhabditis elegans; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; DNA Mutational Analysis; Exome; Female; Forkhead Transcription Factors; Genetic Variation; High-Throughput Nucleotide Sequencing; Humans; Methyl-CpG-Binding Protein 2; mutation; Nerve Tissue Proteins; Protein Serine-Threonine Kinases; Receptors, Nicotinic; Rett Syndrome

Fast inexact mapping using advanced tree exploration on backward search methods. - Salavert, José; Tomás, Andrés; Tárraga, Joaquín; Medina, Ignacio; Dopazo, Joaquin; Blanquer, Ignacio (BMC Bioinformatics, 2015)
BACKGROUND: Short sequence mapping methods for Next Generation Sequencing consist on a combination of seeding techniques followed by local alignment based on dynamic programming approaches. Most seeding algorithms are based on backward search alignment, using the Burrows Wheeler Transform, the Ferragina and Manzini Index or Suffix Arrays. All these backward search algorithms have excellent performance, but their computational cost highly increases when allowing errors. In this paper, we discuss an inexact mapping algorithm based on pruning strategies for search tree exploration over genomic data. RESULTS: The proposed algorithm achieves a 13x speed-up over similar algorithms when allowing 6 base errors, including insertions, deletions and mismatches. This algorithm can deal with 400 bps reads with up to 9 errors in a high quality Illumina dataset. In this example, the algorithm works as a preprocessor that reduces by 55% the number of reads to be aligned. Depending on the aligner the overall execution time is reduced between 20-40%. CONCLUSIONS: Although not intended as a complete sequence mapping tool, the proposed algorithm could be used as a preprocessing step to modern sequence mappers. This step significantly reduces the number reads to be aligned, accelerating overall alignment time. Furthermore, this algorithm could be used for accelerating the seeding step of already available sequence mappers. In addition, an out-of-core index has been implemented for working with large genomes on systems without expensive memory configurations.
Keywords: Algorithms; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Alignment; Sequence Analysis, DNA; Software

A Pan-Cancer Catalogue of Cancer Driver Protein Interaction Interfaces. - Porta-Pardo, Eduard; García-Alonso, Luz; Hrabe, Thomas; Dopazo, Joaquin; Godzik, Adam (PLoS Comput Biol, 2015)
Despite their importance in maintaining the integrity of all cellular pathways, the role of mutations on protein-protein interaction (PPI) interfaces as cancer drivers has not been systematically studied. Here we analyzed the mutation patterns of the PPI interfaces from 10,028 proteins in a pan-cancer cohort of 5,989 tumors from 23 projects of The Cancer Genome Atlas (TCGA) to find interfaces enriched in somatic missense mutations. To that end we use e-Driver, an algorithm to analyze the mutation distribution of specific protein functional regions. We identified 103 PPI interfaces enriched in somatic cancer mutations. 32 of these interfaces are found in proteins coded by known cancer driver genes. The remaining 71 interfaces are found in proteins that have not been previously identified as cancer drivers even that, in most cases, there is an extensive literature suggesting they play an important role in cancer. Finally, we integrate these findings with clinical information to show how tumors apparently driven by the same gene have different behaviors, including patient outcomes, depending on which specific interfaces are mutated.
Keywords: Animals; Base Sequence; Biomarkers, Tumor; Catalogs as Topic; Chromosome Mapping; Computer Simulation; DNA Mutational Analysis; Genetic Predisposition to Disease; Humans; Models, Genetic; Molecular Sequence Data; mutation; Neoplasm Proteins; Neoplasms; Polymorphism, Single Nucleotide; Protein Interaction Mapping; Signal Transduction

Re-evaluation casts doubt on the pathogenicity of homozygous USH2A p.C759F. - Pozo, María González-Del; Bravo-Gil, Nereida; Méndez-Vidal, Cristina; Montero-de-Espinosa, Ignacio; Millán, José M; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (Am J Med Genet A, 2015)
Mutations in USH2A are a common cause of Retinitis Pigmentosa (RP). Among the most frequently reported USH2A variants, c.2276G>T (p.C759F) has been found in both affected and healthy individuals. The pathogenicity of this variant remains controversial since it was detected in homozygosity in two healthy siblings of a Spanish family (S23), eleven years ago. The fact that these individuals remain asymptomatic today, prompted us to study the presence of other pathogenic variants in this family using targeted resequencing of 26 retinal genes in one of the affected individuals. This approach allowed us to identify one novel pathogenic homozygous mutation in exon 13 of PDE6B (c.1678C>T; p.R560C). This variant cosegregated with the disease and was absent in 200 control individuals. Remarkably, the identified variant in PDE6B corresponds to the mutation responsible of the retinal degeneration in the naturally occurring rd10 mutant mice. To our knowledge, this is the first report of the identification of the rd10 mice mutation in a RP family. These findings, together with a review of the literature, support the hypothesis that homozygous p.C759F mutations are not pathogenic and led us to exclude the implication of p.C759F in the RP of family S23. Our results indicate the need of re-evaluating all families genetically diagnosed with this mutation.
Keywords: Base Sequence; Cyclic Nucleotide Phosphodiesterases, Type 6; Extracellular Matrix Proteins; Gene Library; Humans; Molecular Sequence Data; Mutation, Missense; Pedigree; Retinitis pigmentosa; Sequence Analysis, DNA; Spain

Using activation status of signaling pathways as mechanism-based biomarkers to predict drug sensitivity. - Amadoz, Alicia; Sebastián-Leon, Patricia; Vidal, Enrique; Salavert, Francisco; Dopazo, Joaquin (Sci Rep, 2015)
Many complex traits, as drug response, are associated with changes in biological pathways rather than being caused by single gene alterations. Here, a predictive framework is presented in which gene expression data are recoded into activity statuses of signal transduction circuits (sub-pathways within signaling pathways that connect receptor proteins to final effector proteins that trigger cell actions). Such activity values are used as features by a prediction algorithm which can efficiently predict a continuous variable such as the IC50 value. The main advantage of this prediction method is that the features selected by the predictor, the signaling circuits, are themselves rich-informative, mechanism-based biomarkers which provide insight into or drug molecular mechanisms of action (MoA).
Keywords: Algorithms; Antineoplastic Agents; biomarkers; Cell Line, Tumor; Cell Survival; gene expression; Humans; Lethal Dose 50; Neoplasms; Phosphorylation; Proteins; Signal Transduction

Whole-exome sequencing reveals ZNF408 as a new gene associated with autosomal recessive retinitis pigmentosa with vitreal alterations. - Avila-Fernandez, Almudena; Perez-Carro, Raquel; Corton, Marta; Lopez-Molina, Maria Isabel; Campello, Laura; Garanto, Alejandro; Fernandez-Sanchez, Laura; Duijkers, Lonneke; Lopez-Martinez, Miguel Angel; Riveiro-Alvarez, Rosa; da Silva, Luciana Rodrigues Jacy; Sanchez-Alcudia, Rocío; et al. (Hum Mol Genet, 2015)
Retinitis pigmentosa (RP) is a group of progressive inherited retinal dystrophies that cause visual impairment as a result of photoreceptor cell death. RP is heterogeneous, both clinically and genetically making difficult to establish precise genotype-phenotype correlations. In a Spanish family with autosomal recessive RP (arRP), homozygosity mapping and whole-exome sequencing led to the identification of a homozygous mutation (c.358_359delGT; p.Ala122Leufs*2) in the ZNF408 gene. A screening performed in 217 additional unrelated families revealed another homozygous mutation (c.1621C>T; p.Arg541Cys) in an isolated RP case. ZNF408 encodes a transcription factor that harbors 10 predicted C2H2-type fingers thought to be implicated in DNA binding. To elucidate the ZNF408 role in the retina and the pathogenesis of these mutations we have performed different functional studies. By immunohistochemical analysis in healthy human retina, we identified that ZNF408 is expressed in both cone and rod photoreceptors, in a specific type of amacrine and ganglion cells, and in retinal blood vessels. ZNF408 revealed a cytoplasmic localization and a nuclear distribution in areas corresponding with the euchromatin fraction. Immunolocalization studies showed a partial mislocalization of the p.Arg541Cys mutant protein retaining part of the WT protein in the cytoplasm. Our study demonstrates that ZNF408, previously associated with Familial Exudative Vitreoretinopathy (FEVR), is a new gene causing arRP with vitreous condensations supporting the evidence that this protein plays additional functions into the human retina.
Keywords: Amino Acid Sequence; Animals; Chlorocebus aethiops; Chromosome Mapping; COS Cells; DNA-Binding Proteins; Exome; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Molecular Sequence Data; Mutant Proteins; Pedigree; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis pigmentosa; Transcription Factors

Exome sequencing reveals novel and recurrent mutations with clinical significance in inherited retinal dystrophies. - González-del Pozo, María; Méndez-Vidal, Cristina; Bravo-Gil, Nereida; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (PLoS One, 2014)
This study aimed to identify the underlying molecular genetic cause in four Spanish families clinically diagnosed of Retinitis Pigmentosa (RP), comprising one autosomal dominant RP (adRP), two autosomal recessive RP (arRP) and one with two possible modes of inheritance: arRP or X-Linked RP (XLRP). We performed whole exome sequencing (WES) using NimbleGen SeqCap EZ Exome V3 sample preparation kit and SOLID 5500xl platform. All variants passing filter criteria were validated by Sanger sequencing to confirm familial segregation and the absence in local control population. This strategy allowed the detection of: (i) one novel heterozygous splice-site deletion in RHO, c.937-2_944del, (ii) one rare homozygous mutation in C2orf71, c.1795T>C; p.Cys599Arg, not previously associated with the disease, (iii) two heterozygous null mutations in ABCA4, c.2041C>T; p.R681* and c.6088C>T; p.R2030*, and (iv) one mutation, c.2405-2406delAG; p.Glu802Glyfs*31 in the ORF15 of RPGR. The molecular findings for RHO and C2orf71 confirmed the initial diagnosis of adRP and arRP, respectively, while patients with the two ABCA4 mutations, both previously associated with Stargardt disease, presented symptoms of RP with early macular involvement. Finally, the X-Linked inheritance was confirmed for the family with the RPGR mutation. This latter finding allowed the inclusion of carrier sisters in our preimplantational genetic diagnosis program.
Keywords: Adolescent; Adult; Amino Acid Sequence; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Family; Female; Humans; Inheritance Patterns; Male; Middle Aged; Molecular Sequence Data; mutation; Pedigree; Retinal Dystrophies; Rhodopsin

ngsCAT: a tool to assess the efficiency of targeted enrichment sequencing. - López-Domingo, Francisco J; Florido, Javier P; Rueda, Antonio; Dopazo, Joaquin; Santoyo-López, Javier (Bioinformatics, 2014)
MOTIVATION: Targeted enrichment sequencing by next-generation sequencing is a common approach to interrogate specific loci or the whole exome in the human genome. The efficiency and the lack of bias in the enrichment process need to be assessed as a quality control step before performing downstream analysis of the sequence data. Tools that can report on the sensitivity, specificity, uniformity and other enrichment-specific features are needed. RESULTS: We have implemented the next-generation sequencing data Capture Assessment Tool (ngsCAT), a tool that takes the information of the mapped reads and the coordinates of the targeted regions as input files, and generates a report with metrics and figures that allows the evaluation of the efficiency of the enrichment process. The tool can also take as input the information of two samples allowing the comparison of two different experiments. AVAILABILITY AND IMPLEMENTATION: Documentation and downloads for ngsCAT can be found at http://www.bioinfomgp.org/ngscat.
Keywords: Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Novel RP1 mutations and a recurrent BBS1 variant explain the co-existence of two distinct retinal phenotypes in the same pedigree. - Méndez-Vidal, Cristina; Bravo-Gil, Nereida; González-del Pozo, María; Vela-Boza, Alicia; Dopazo, Joaquin; Borrego, Salud; Antiňolo, Guillermo (BMC Genet, 2014)
BACKGROUND: Molecular diagnosis of Inherited Retinal Dystrophies (IRD) has long been challenging due to the extensive clinical and genetic heterogeneity present in this group of disorders. Here, we describe the clinical application of an integrated next-generation sequencing approach to determine the underlying genetic defects in a Spanish family with a provisional clinical diagnosis of autosomal recessive Retinitis Pigmentosa (arRP). RESULTS: Exome sequencing of the index patient resulted in the identification of the homozygous BBS1 p.M390R mutation. Sanger sequencing of additional members of the family showed lack of co-segregation of the p.M390R variant in some individuals. Clinical reanalysis indicated co-ocurrence of two different phenotypes in the same family: Bardet-Biedl syndrome in the individual harboring the BBS1 mutation and non-syndromic arRP in extended family members. To identify possible causative mutations underlying arRP, we conducted disease-targeted gene sequencing using a panel of 26 IRD genes. The in-house custom panel was validated using 18 DNA samples known to harbor mutations in relevant genes. All variants were redetected, indicating a high mutation detection rate. This approach allowed the identification of two novel heterozygous null mutations in RP1 (c.4582_4585delATCA; p.I1528Vfs*10 and c.5962dupA; p.I1988Nfs*3) which co-segregated with the disease in arRP patients. Additionally, a mutational screening in 96 patients of our cohort with genetically unresolved IRD revealed the presence of the c.5962dupA mutation in one unrelated family. CONCLUSIONS: The combination of molecular findings for RP1 and BBS1 genes through exome and gene panel sequencing enabled us to explain the co-existence of two different retinal phenotypes in a family. The identification of two novel variants in RP1 suggests that the use of panels containing the prevalent genes of a particular population, together with an optimized data analysis pipeline, is an efficient and cost-effective approach that can be reliably implemented into the routine diagnostic process of diverse inherited retinal disorders. Moreover, the identification of these novel variants in two unrelated families supports the relatively high prevalence of RP1 mutations in Spanish population and the role of private mutations for commonly mutated genes, while extending the mutational spectrum of RP1.
Keywords: Bardet-Biedl Syndrome; Base Sequence; Case-Control Studies; DNA Mutational Analysis; Eye Proteins; Genes, Recessive; Genetic Association Studies; Humans; Microsatellite Repeats; Microtubule-Associated Proteins; Mutation, Missense; Pedigree; Phenotype; Retina; Retinitis pigmentosa

The role of the interactome in the maintenance of deleterious variability in human populations. - García-Alonso, Luz; Jiménez-Almazán, Jorge; Carbonell-Caballero, José; Vela-Boza, Alicia; Santoyo-López, Javier; Antiňolo, Guillermo; Dopazo, Joaquin (Mol Syst Biol, 2014)
Recent genomic projects have revealed the existence of an unexpectedly large amount of deleterious variability in the human genome. Several hypotheses have been proposed to explain such an apparently high mutational load. However, the mechanisms by which deleterious mutations in some genes cause a pathological effect but are apparently innocuous in other genes remain largely unknown. This study searched for deleterious variants in the 1,000 genomes populations, as well as in a newly sequenced population of 252 healthy Spanish individuals. In addition, variants causative of monogenic diseases and somatic variants from 41 chronic lymphocytic leukaemia patients were analysed. The deleterious variants found were analysed in the context of the interactome to understand the role of network topology in the maintenance of the observed mutational load. Our results suggest that one of the mechanisms whereby the effect of these deleterious variants on the phenotype is suppressed could be related to the configuration of the protein interaction network. Most of the deleterious variants observed in healthy individuals are concentrated in peripheral regions of the interactome, in combinations that preserve their connectivity, and have a marginal effect on interactome integrity. On the contrary, likely pathogenic cancer somatic deleterious variants tend to occur in internal regions of the interactome, often with associated structural consequences. Finally, variants causative of monogenic diseases seem to occupy an intermediate position. Our observations suggest that the real pathological potential of a variant might be more a systems property rather than an intrinsic property of individual proteins.
Keywords: Alleles; Exome; Gene Library; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Models, Genetic; mutation; Phenotype; Protein Conformation; Protein Interaction Maps; Sequence Analysis, DNA; Whites

Two novel mutations in the BCKDK (branched-chain keto-acid dehydrogenase kinase) gene are responsible for a neurobehavioral deficit in two pediatric unrelated patients. - García-Cazorla, Angels; Oyarzabal, Alfonso; Fort, Joana; Robles, Concepción; Castejón, Esperanza; Ruiz-Sala, Pedro; Bodoy, Susanna; Merinero, Begoña; Lopez-Sala, Anna; Dopazo, Joaquin; Nunes, Virginia; Ugarte, Magdalena; et al. (Hum Mutat, 2014)
Inactivating mutations in the BCKDK gene, which codes for the kinase responsible for the negative regulation of the branched-chain α-keto acid dehydrogenase complex (BCKD), have recently been associated with a form of autism in three families. In this work, two novel exonic BCKDK mutations, c.520C>G/p.R174G and c.1166T>C/p.L389P, were identified at the homozygous state in two unrelated children with persistently reduced body fluid levels of branched-chain amino acids (BCAAs), developmental delay, microcephaly, and neurobehavioral abnormalities. Functional analysis of the mutations confirmed the missense character of the c.1166T>C change and showed a splicing defect r.[520c>g;521_543del]/p.R174Gfs1*, for c.520C>G due to the presence of a new donor splice site. Mutation p.L389P showed total loss of kinase activity. Moreover, patient-derived fibroblasts showed undetectable (p.R174Gfs1*) or barely detectable (p.L389P) levels of BCKDK protein and its phosphorylated substrate (phospho-E1α), resulting in increased BCKD activity and the very rapid BCAA catabolism manifested by the patients' clinical phenotype. Based on these results, a protein-rich diet plus oral BCAA supplementation was implemented in the patient homozygous for p.R174Gfs1*. This treatment normalized plasma BCAA levels and improved growth, developmental and behavioral variables. Our results demonstrate that BCKDK mutations can result in neurobehavioral deficits in humans and support the rationale for dietary intervention.
Keywords: Amino Acids, Branched-Chain; Developmental Disabilities; Fibroblasts; Humans; Male; Mutation, Missense; Nervous System Diseases; Pediatrics; Protein Kinases

Defining the genomic signature of totipotency and pluripotency during early human development. - Galan, Amparo; Diaz-Gimeno, Patricia; Poo, Maria Eugenia; Valbuena, Diana; Sanchez, Eva; Ruiz, Veronica; Dopazo, Joaquin; Montaner, David; Conesa, Ana; Simon, Carlos (PLoS One, 2013)
The genetic mechanisms governing human pre-implantation embryo development and the in vitro counterparts, human embryonic stem cells (hESCs), still remain incomplete. Previous global genome studies demonstrated that totipotent blastomeres from day-3 human embryos and pluripotent inner cell masses (ICMs) from blastocysts, display unique and differing transcriptomes. Nevertheless, comparative gene expression analysis has revealed that no significant differences exist between hESCs derived from blastomeres versus those obtained from ICMs, suggesting that pluripotent hESCs involve a new developmental progression. To understand early human stages evolution, we developed an undifferentiation network signature (UNS) and applied it to a differential gene expression profile between single blastomeres from day-3 embryos, ICMs and hESCs. This allowed us to establish a unique signature composed of highly interconnected genes characteristic of totipotency (61 genes), in vivo pluripotency (20 genes), and in vitro pluripotency (107 genes), and which are also proprietary according to functional analysis. This systems biology approach has led to an improved understanding of the molecular and signaling processes governing human pre-implantation embryo development, as well as enabling us to comprehend how hESCs might adapt to in vitro culture conditions.
Keywords: Blastocyst Inner Cell Mass; Blastomeres; Cell Differentiation; Embryonic Development; Embryonic Stem Cells; Gene Expression Profiling; Gene Regulatory Networks; Genome, Human; Humans; Molecular Sequence Annotation; Pluripotent Stem Cells; Totipotent Stem Cells

Exome sequencing identifies a new mutation in SERAC1 in a patient with 3-methylglutaconic aciduria. - Tort, Frederic; García-Silva, María Teresa; Ferrer-Cortès, Xènia; Navarro-Sastre, Aleix; Garcia-Villoria, Judith; Coll, Maria Josep; Vidal, Enrique; Jiménez-Almazán, Jorge; Dopazo, Joaquin; Briones, Paz; Elpeleg, Orly; Ribes, Antonia (Mol Genet Metab, 2013)
3-Methylglutaconic aciduria (3-MGA-uria) is a heterogeneous group of syndromes characterized by an increased excretion of 3-methylglutaconic and 3-methylglutaric acids. Five types of 3-MGA-uria (I to V) with different clinical presentations have been described. Causative mutations in TAZ, OPA3, DNAJC19, ATP12, ATP5E, and TMEM70 have been identified. After excluding the known genetic causes of 3-MGA-uria we used exome sequencing to investigate a patient with Leigh syndrome and 3-MGA-uria. We identified a homozygous variant in SERAC1 (c.202C>T; p.Arg68*), that generates a premature stop codon at position 68 of SERAC1 protein. Western blot analysis in patient's fibroblasts showed a complete absence of SERAC1 that was consistent with the prediction of a truncated protein and supports the pathogenic role of the mutation. During the course of this project a parallel study identified mutations in SERAC1 as the genetic cause of the disease in 15 patients with MEGDEL syndrome, which was compatible with the clinical and biochemical phenotypes of the patient described here. In addition, our patient developed microcephaly and optic atrophy, two features not previously reported in MEGDEL syndrome. We highlight the usefulness of exome sequencing to reveal the genetic bases of human rare diseases even if only one affected individual is available.
Keywords: Adolescent; Adult; Carboxylic Ester Hydrolases; Child; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Metabolism, Inborn Errors; mutation

Inferring the functional effect of gene expression changes in signaling pathways. - Sebastián-Leon, Patricia; Carbonell, José; Salavert, Francisco; Sánchez, Rubén; Medina, Ignacio; Dopazo, Joaquin (Nucleic Acids Res, 2013)
Signaling pathways constitute a valuable source of information that allows interpreting the way in which alterations in gene activities affect to particular cell functionalities. There are web tools available that allow viewing and editing pathways, as well as representing experimental data on them. However, few methods aimed to identify the signaling circuits, within a pathway, associated to the biological problem studied exist and none of them provide a convenient graphical web interface. We present PATHiWAYS, a web-based signaling pathway visualization system that infers changes in signaling that affect cell functionality from the measurements of gene expression values in typical expression microarray case-control experiments. A simple probabilistic model of the pathway is used to estimate the probabilities for signal transmission from any receptor to any final effector molecule (taking into account the pathway topology) using for this the individual probabilities of gene product presence/absence inferred from gene expression values. Significant changes in these probabilities allow linking different cell functionalities triggered by the pathway to the biological problem studied. PATHiWAYS is available at: http://pathiways.babelomics.org/.
Keywords: Animals; Humans; Internet; Mice; Models, Statistical; Receptors, Cell Surface; Signal Transduction; Software; Transcriptome

Mammosphere formation in breast carcinoma cell lines depends upon expression of E-cadherin. - Manuel Iglesias, Juan; Beloqui, Izaskun; Garcia-Garcia, Francisco; Leis, Olatz; Vazquez-Martin, Alejandro; Eguiara, Arrate; Cufi, Silvia; Pavon, Andres; Menendez, Javier A; Dopazo, Joaquin; Martin, Angel G (PLoS One, 2013)
Tumors are heterogeneous at the cellular level where the ability to maintain tumor growth resides in discrete cell populations. Floating sphere-forming assays are broadly used to test stem cell activity in tissues, tumors and cell lines. Spheroids are originated from a small population of cells with stem cell features able to grow in suspension culture and behaving as tumorigenic in mice. We tested the ability of eleven common breast cancer cell lines representing the major breast cancer subtypes to grow as mammospheres, measuring the ability to maintain cell viability upon serial non-adherent passage. Only MCF7, T47D, BT474, MDA-MB-436 and JIMT1 were successfully propagated as long-term mammosphere cultures, measured as the increase in the number of viable cells upon serial non-adherent passages. Other cell lines tested (SKBR3, MDA-MB-231, MDA-MB-468 and MDA-MB-435) formed cell clumps that can be disaggregated mechanically, but cell viability drops dramatically on their second passage. HCC1937 and HCC1569 cells formed typical mammospheres, although they could not be propagated as long-term mammosphere cultures. All the sphere forming lines but MDA-MB-436 express E-cadherin on their surface. Knock down of E-cadherin expression in MCF-7 cells abrogated its ability to grow as mammospheres, while re-expression of E-cadherin in SKBR3 cells allow them to form mammospheres. Therefore, the mammosphere assay is suitable to reveal stem like features in breast cancer cell lines that express E-cadherin.
Keywords: Breast Neoplasms; Cadherins; Cell Line, Tumor; Cell Proliferation; Cluster Analysis; Female; gene expression; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Knockdown Techniques; Humans; MCF-7 Cells; Neoplastic Stem Cells; Spheroids, Cellular; Tumor Cells, Cultured

Novel genes detected by transcriptional profiling from whole-blood cells in patients with early onset of acute coronary syndrome. - Silbiger, Vivian N; Luchessi, André D; Hirata, Rosário D C; Lima-Neto, Lídio G; Cavichioli, Débora; Carracedo, Ángel; Brión, Maria; Dopazo, Joaquin; Garcia-Garcia, Francisco; Dos Santos, Elizabete S; Ramos, Rui F; Sampaio, Marcelo F; et al. (Clin Chim Acta, 2013)
BACKGROUND: Genome-wide expression analysis using microarrays has been used as a research strategy to discovery new biomarkers and candidate genes for a number of diseases. We aim to find new biomarkers for the prediction of acute coronary syndrome (ACS) with a differentially expressed mRNA profiling approach using whole genomic expression analysis in a peripheral blood cell model from patients with early ACS. METHODS AND RESULTS: This study was carried out in two phases. On phase 1 a restricted clinical criteria (ACS-Ph1, n=9 and CG-Ph1, n=6) was used in order to select potential mRNA biomarkers candidates. A subsequent phase 2 study was performed using selected phase 1 markers analyzed by RT-qPCR using a larger and independent casuistic (ACS-Ph2, n=74 and CG-Ph2, n=41). A total of 549 genes were found to be differentially expressed in the first 48 h after the ACS-Ph1. Technical and biological validation further confirmed that ALOX15, AREG, BCL2A1, BCL2L1, CA1, COX7B, ECHDC3, IL18R1, IRS2, KCNE1, MMP9, MYL4 and TREML4, are differentially expressed in both phases of this study. CONCLUSIONS: Transcriptomic analysis by microarray technology demonstrated differential expression during a 48 h time course suggesting a potential use of some of these genes as biomarkers for very early stages of ACS, as well as for monitoring early cardiac ischemic recovery.
Keywords: Acute Coronary Syndrome; Acute-Phase Proteins; Adult; biomarkers; Blood Cells; Early Diagnosis; gene expression; Gene Expression Profiling; Humans; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; RNA, Messenger; Transcriptome

Pathways systematically associated to Hirschsprung's disease. - Fernández, Raquel M; Bleda, Marta; Luzón-Toro, Berta; García-Alonso, Luz; Arnold, Stacey; Sribudiani, Yunia; Besmond, Claude; Lantieri, Francesca; Doan, Betty; Ceccherini, Isabella; Lyonnet, Stanislas; Hofstra, Robert Mw; et al. (Orphanet J Rare Dis, 2013)
Despite it has been reported that several loci are involved in Hirschsprung's disease, the molecular basis of the disease remains yet essentially unknown. The study of collective properties of modules of functionally-related genes provides an efficient and sensitive statistical framework that can overcome sample size limitations in the study of rare diseases. Here, we present the extension of a previous study of a Spanish series of HSCR trios to an international cohort of 162 HSCR trios to validate the generality of the underlying functional basis of the Hirschsprung's disease mechanisms previously found. The Pathway-Based Analysis (PBA) confirms a strong association of gene ontology (GO) modules related to signal transduction and its regulation, enteric nervous system (ENS) formation and other processes related to the disease. In addition, network analysis recovers sub-networks significantly associated to the disease, which contain genes related to the same functionalities, thus providing an independent validation of these findings. The functional profiles of association obtained for patients populations from different countries were compared to each other. While gene associations were different at each series, the main functional associations were identical in all the five populations. These observations would also explain the reported low reproducibility of associations of individual disease genes across populations.
Keywords: Female; Genetic Predisposition to Disease; Genotype; Hirschsprung Disease; Humans; Male; Polymorphism, Single Nucleotide

Role of CPI-17 in restoring skin homoeostasis in cutaneous field of cancerization: effects of topical application of a film-forming medical device containing photolyase and UV filters. - Puig-Butille, Joan Anton; Malvehy, Josep; Potrony, Miriam; Trullas, Carles; Garcia-Garcia, Francisco; Dopazo, Joaquin; Puig, Susana (Exp Dermatol, 2013)
Cutaneous field of cancerization (CFC) is caused in part by the carcinogenic effect of the cyclobutane pyrimidine dimers CPD and 6-4 photoproducts (6-4PPs). Photoreactivation is carried out by photolyases which specifically recognize and repair both photoproducts. The study evaluates the molecular effects of topical application of a film-forming medical device containing photolyase and UV filters on the precancerous field in AK from seven patients. Skin improvement after treatment was confirmed in all patients by histopathological and molecular assessment. A gene set analysis showed that skin recovery was associated with biological processes involved in tissue homoeostasis and cell maintenance. The CFC response was associated with over-expression of the CPI-17 gene, and a dependence on the initial expression level was observed (P = 0.001). Low CPI-17 levels were directly associated with pro-inflammatory genes such as TNF (P = 0.012) and IL-1B (P = 0.07). Our results suggest a role for CPI-17 in restoring skin homoeostasis in CFC lesions.
Keywords: Administration, Topical; Adult; Aged; Aged, 80 and over; Biopsy; Deoxyribodipyrimidine Photo-Lyase; Female; Gene Expression Profiling; Gene Expression Regulation, Enzymologic; Gene Expression Regulation, Neoplastic; Homeostasis; Humans; Inflammation; Intracellular Signaling Peptides and Proteins; Liposomes; Male; Middle Aged; Muscle Proteins; Phenotype; Phosphoprotein Phosphatases; Reactive Oxygen Species; Skin; Skin Neoplasms; Ultraviolet Rays

Discovering the hidden sub-network component in a ranked list of genes or proteins derived from genomic experiments. - García-Alonso, Luz; Alonso, Roberto; Vidal, Enrique; Amadoz, Alicia; De Maria, Alejandro; Minguez, Pablo; Medina, Ignacio; Dopazo, Joaquin (Nucleic Acids Res, 2012)
Genomic experiments (e.g. differential gene expression, single-nucleotide polymorphism association) typically produce ranked list of genes. We present a simple but powerful approach which uses protein-protein interaction data to detect sub-networks within such ranked lists of genes or proteins. We performed an exhaustive study of network parameters that allowed us concluding that the average number of components and the average number of nodes per component are the parameters that best discriminate between real and random networks. A novel aspect that increases the efficiency of this strategy in finding sub-networks is that, in addition to direct connections, also connections mediated by intermediate nodes are considered to build up the sub-networks. The possibility of using of such intermediate nodes makes this approach more robust to noise. It also overcomes some limitations intrinsic to experimental designs based on differential expression, in which some nodes are invariant across conditions. The proposed approach can also be used for candidate disease-gene prioritization. Here, we demonstrate the usefulness of the approach by means of several case examples that include a differential expression analysis in Fanconi Anemia, a genome-wide association study of bipolar disorder and a genome-scale study of essentiality in cancer genes. An efficient and easy-to-use web interface (available at http://www.babelomics.org) based on HTML5 technologies is also provided to run the algorithm and represent the network.
Keywords: Bipolar Disorder; Fanconi Anemia; Gene Regulatory Networks; Genes, Neoplasm; Genome-Wide Association Study; Genomics; Humans; Protein Interaction Mapping

Extensive translatome remodeling during ER stress response in mammalian cells. - Ventoso, Iván; Kochetov, Alex; Montaner, David; Dopazo, Joaquin; Santoyo, Javier (PLoS One, 2012)
In this work we have described the translatome of two mammalian cell lines, NIH3T3 and Jurkat, by scoring the relative polysome association of ∼10,000 mRNA under normal and ER stress conditions. We have found that translation efficiencies of mRNA correlated poorly with transcript abundance, although a general tendency was observed so that the highest translation efficiencies were found in abundant mRNA. Despite the differences found between mouse (NIH3T3) and human (Jurkat) cells, both cell types share a common translatome composed by ∼800-900 mRNA that encode proteins involved in basic cellular functions. Upon stress, an extensive remodeling in translatomes was observed so that translation of ∼50% of mRNA was inhibited in both cell types, this effect being more dramatic for those mRNA that accounted for most of the cell translation. Interestingly, we found two subsets comprising 1000-1500 mRNA whose translation resisted or was induced by stress. Translation arrest resistant class includes many mRNA encoding aminoacyl tRNA synthetases, ATPases and enzymes involved in DNA replication and stress response such as BiP. This class of mRNA is characterized by high translation rates in both control and stress conditions. Translation inducible class includes mRNA whose translation was relieved after stress, showing a high enrichment in early response transcription factors of bZIP and zinc finger C2H2 classes. Unlike yeast, a general coordination between changes in translation and transcription upon stress (potentiation) was not observed in mammalian cells. Among the different features of mRNA analyzed, we found a relevant association of translation efficiency with the presence of upstream ATG in the 5'UTR and with the length of coding sequence of mRNA, and a looser association with other parameters such as the length and the G+C content of 5'UTR. A model for translatome remodeling during the acute phase of stress response in mammalian cells is proposed.
Keywords: Animals; Endoplasmic Reticulum Stress; Humans; Jurkat Cells; Mice; NIH 3T3 Cells; Oligonucleotide Array Sequence Analysis; Protein Biosynthesis; RNA, Messenger; Transcription, Genetic

Four new loci associations discovered by pathway-based and network analyses of the genome-wide variability profile of Hirschsprung's disease. - Fernández, Raquel Ma; Bleda, Marta; Núñez-Torres, Rocío; Medina, Ignacio; Luzón-Toro, Berta; García-Alonso, Luz; Torroglosa, Ana; Marbà, Martina; Enguix-Riego, Ma Valle; Montaner, David; Antiňolo, Guillermo; Dopazo, Joaquin; et al. (Orphanet J Rare Dis, 2012)
Finding gene associations in rare diseases is frequently hampered by the reduced numbers of patients accessible. Conventional gene-based association tests rely on the availability of large cohorts, which constitutes a serious limitation for its application in this scenario. To overcome this problem we have used here a combined strategy in which a pathway-based analysis (PBA) has been initially conducted to prioritize candidate genes in a Spanish cohort of 53 trios of short-segment Hirschsprung's disease. Candidate genes have been further validated in an independent population of 106 trios. The study revealed a strong association of 11 gene ontology (GO) modules related to signal transduction and its regulation, enteric nervous system (ENS) formation and other HSCR-related processes. Among the preselected candidates, a total of 4 loci, RASGEF1A, IQGAP2, DLC1 and CHRNA7, related to signal transduction and migration processes, were found to be significantly associated to HSCR. Network analysis also confirms their involvement in the network of already known disease genes. This approach, based on the study of functionally-related gene sets, requires of lower sample sizes and opens new opportunities for the study of rare diseases.
Keywords: Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hirschsprung Disease; Humans; Male

IL1β induces mesenchymal stem cells migration and leucocyte chemotaxis through NF-κB. - Carrero, Rubén; Cerrada, Inmaculada; Lledó, Elisa; Dopazo, Joaquin; Garcia-Garcia, Francisco; Rubio, Mari-Paz; Trigueros, César; Dorronsoro, Akaitz; Ruiz-Sauri, Amparo; Montero, José Anastasio; Sepúlveda, Pilar (Stem Cell Rev Rep, 2012)
Mesenchymal stem cells are often transplanted into inflammatory environments where they are able to survive and modulate host immune responses through a poorly understood mechanism. In this paper we analyzed the responses of MSC to IL-1β: a representative inflammatory mediator. Microarray analysis of MSC treated with IL-1β revealed that this cytokine activateds a set of genes related to biological processes such as cell survival, cell migration, cell adhesion, chemokine production, induction of angiogenesis and modulation of the immune response. Further more detailed analysis by real-time PCR and functional assays revealed that IL-1β mainly increaseds the production of chemokines such as CCL5, CCL20, CXCL1, CXCL3, CXCL5, CXCL6, CXCL10, CXCL11 and CX(3)CL1, interleukins IL-6, IL-8, IL23A, IL32, Toll-like receptors TLR2, TLR4, CLDN1, metalloproteins MMP1 and MMP3, growth factors CSF2 and TNF-α, together with adhesion molecules ICAM1 and ICAM4. Functional analysis of MSC proliferation, migration and adhesion to extracellular matrix components revealed that IL-1β did not affect proliferation but also served to induce the secretion of trophic factors and adhesion to ECM components such as collagen and laminin. IL-1β treatment enhanced the ability of MSC to recruit monocytes and granulocytes in vitro. Blockade of NF-κβ transcription factor activation with IκB kinase beta (IKKβ) shRNA impaired MSC migration, adhesion and leucocyte recruitment, induced by IL-1β demonstrating that NF-κB pathway is an important downstream regulator of these responses. These findings are relevant to understanding the biological responses of MSC to inflammatory environments.
Keywords: Cell Adhesion; Cell Movement; Cell Proliferation; Chemokines; Chemotaxis, Leukocyte; Collagen; Fibronectins; Gene Expression Profiling; Gene Knockdown Techniques; HEK293 Cells; Humans; I-kappa B Kinase; Inflammation Mediators; Intercellular Signaling Peptides and Proteins; Interleukin-1beta; Laminin; Leukocytes; Mesenchymal Stem Cells; NF-kappa B; Oligonucleotide Array Sequence Analysis; RNA Interference; Signal Transduction

SNPeffect 4.0: on-line prediction of molecular and structural effects of protein-coding variants. - De Baets, Greet; Van Durme, Joost; Reumers, Joke; Maurer-Stroh, Sebastian; Vanhee, Peter; Dopazo, Joaquin; Schymkowitz, Joost; Rousseau, Frederic (Nucleic Acids Res, 2012)
Single nucleotide variants (SNVs) are, together with copy number variation, the primary source of variation in the human genome and are associated with phenotypic variation such as altered response to drug treatment and susceptibility to disease. Linking structural effects of non-synonymous SNVs to functional outcomes is a major issue in structural bioinformatics. The SNPeffect database (http://snpeffect.switchlab.org) uses sequence- and structure-based bioinformatics tools to predict the effect of protein-coding SNVs on the structural phenotype of proteins. It integrates aggregation prediction (TANGO), amyloid prediction (WALTZ), chaperone-binding prediction (LIMBO) and protein stability analysis (FoldX) for structural phenotyping. Additionally, SNPeffect holds information on affected catalytic sites and a number of post-translational modifications. The database contains all known human protein variants from UniProt, but users can now also submit custom protein variants for a SNPeffect analysis, including automated structure modeling. The new meta-analysis application allows plotting correlations between phenotypic features for a user-selected set of variants.
Keywords: Databases, Protein; Humans; Internet; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Protein Conformation; Proteins

Whole-genome bisulfite DNA sequencing of a DNMT3B mutant patient. - Heyn, Holger; Vidal, Enrique; Sayols, Sergi; Sanchez-Mut, Jose V; Moran, Sebastian; Medina, Ignacio; Sandoval, Juan; Simó-Riudalbas, Laia; Szczesna, Karolina; Huertas, Dori; Gatto, Sole; Matarazzo, Maria R; et al. (Epigenetics, 2012)
The immunodeficiency, centromere instability and facial anomalies (ICF) syndrome is associated to mutations of the DNA methyl-transferase DNMT3B, resulting in a reduction of enzyme activity. Aberrant expression of immune system genes and hypomethylation of pericentromeric regions accompanied by chromosomal instability were determined as alterations driving the disease phenotype. However, so far only technologies capable to analyze single loci were applied to determine epigenetic alterations in ICF patients. In the current study, we performed whole-genome bisulphite sequencing to assess alteration in DNA methylation at base pair resolution. Genome-wide we detected a decrease of methylation level of 42%, with the most profound changes occurring in inactive heterochromatic regions, satellite repeats and transposons. Interestingly, transcriptional active loci and ribosomal RNA repeats escaped global hypomethylation. Despite a genome-wide loss of DNA methylation the epigenetic landscape and crucial regulatory structures were conserved. Remarkably, we revealed a mislocated activity of mutant DNMT3B to H3K4me1 loci resulting in hypermethylation of active promoters. Functionally, we could associate alterations in promoter methylation with the ICF syndrome immunodeficient phenotype by detecting changes in genes related to the B-cell receptor mediated maturation pathway.
Keywords: B-Lymphocytes; Cell Line, Transformed; Child, Preschool; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Epigenesis, Genetic; Face; Female; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; mutation; Primary Immunodeficiency Diseases; Sequence Analysis, DNA; Sulfites

Differential expression in RNA-seq: a matter of depth. - Tarazona, Sonia; García-Alcalde, Fernando; Dopazo, Joaquin; Ferrer, Alberto; Conesa, Ana (Genome Res, 2011)
Next-generation sequencing (NGS) technologies are revolutionizing genome research, and in particular, their application to transcriptomics (RNA-seq) is increasingly being used for gene expression profiling as a replacement for microarrays. However, the properties of RNA-seq data have not been yet fully established, and additional research is needed for understanding how these data respond to differential expression analysis. In this work, we set out to gain insights into the characteristics of RNA-seq data analysis by studying an important parameter of this technology: the sequencing depth. We have analyzed how sequencing depth affects the detection of transcripts and their identification as differentially expressed, looking at aspects such as transcript biotype, length, expression level, and fold-change. We have evaluated different algorithms available for the analysis of RNA-seq and proposed a novel approach--NOISeq--that differs from existing methods in that it is data-adaptive and nonparametric. Our results reveal that most existing methodologies suffer from a strong dependency on sequencing depth for their differential expression calls and that this results in a considerable number of false positives that increases as the number of reads grows. In contrast, our proposed method models the noise distribution from the actual data, can therefore better adapt to the size of the data set, and is more effective in controlling the rate of false discoveries. This work discusses the true potential of RNA-seq for studying regulation at low expression ranges, the noise within RNA-seq data, and the issue of replication.
Keywords: Algorithms; Expressed Sequence Tags; Gene Expression Profiling; Gene Expression Regulation; Humans; Models, Genetic; Oligonucleotide Array Sequence Analysis

Evidence for short-time divergence and long-time conservation of tissue-specific expression after gene duplication. - Huerta-Cepas, Jaime; Dopazo, Joaquin; Huynen, Martijn A; Gabaldón, Toni (Brief Bioinform, 2011)
Gene duplication is one of the main mechanisms by which genomes can acquire novel functions. It has been proposed that the retention of gene duplicates can be associated to processes of tissue expression divergence. These models predict that acquisition of divergent expression patterns should be acquired shortly after the duplication, and that larger divergence in tissue expression would be expected for paralogs, as compared to orthologs of a similar age. Many studies have shown that gene duplicates tend to have divergent expression patterns and that gene family expansions are associated with high levels of tissue specificity. However, the timeframe in which these processes occur have rarely been investigated in detail, particularly in vertebrates, and most analyses do not include direct comparisons of orthologs as a baseline for the expected levels of tissue specificity in absence of duplications. To assess the specific contribution of duplications to expression divergence, we combine here phylogenetic analyses and expression data from human and mouse. In particular, we study differences in spatial expression among human-mouse paralogs, specifically duplicated after the radiation of mammals, and compare them to pairs of orthologs in the same species. Our results show that gene duplication leads to increased levels of tissue specificity and that this tends to occur promptly after the duplication event.
Keywords: Animals; Conserved Sequence; Evolution, Molecular; Gene Duplication; gene expression; Genome; Humans; Mice; Organ Specificity

Large-scale transcriptional profiling and functional assays reveal important roles for Rho-GTPase signalling and SCL during haematopoietic differentiation of human embryonic stem cells. - Yung, Sun; Ledran, Maria; Moreno-Gimeno, Inmaculada; Conesa, Ana; Montaner, David; Dopazo, Joaquin; Dimmick, Ian; Slater, Nicholas J; Marenah, Lamin; Real, Pedro J; Paraskevopoulou, Iliana; Bisbal, Viviana; et al. (Hum Mol Genet, 2011)
Understanding the transcriptional cues that direct differentiation of human embryonic stem cells (hESCs) and human-induced pluripotent stem cells to defined and functional cell types is essential for future clinical applications. In this study, we have compared transcriptional profiles of haematopoietic progenitors derived from hESCs at various developmental stages of a feeder- and serum-free differentiation method and show that the largest transcriptional changes occur during the first 4 days of differentiation. Data mining on the basis of molecular function revealed Rho-GTPase signalling as a key regulator of differentiation. Inhibition of this pathway resulted in a significant reduction in the numbers of emerging haematopoietic progenitors throughout the differentiation window, thereby uncovering a previously unappreciated role for Rho-GTPase signalling during human haematopoietic development. Our analysis indicated that SCL was the 11th most upregulated transcript during the first 4 days of the hESC differentiation process. Overexpression of SCL in hESCs promoted differentiation to meso-endodermal lineages, the emergence of haematopoietic and erythro-megakaryocytic progenitors and accelerated erythroid differentiation. Importantly, intrasplenic transplantation of SCL-overexpressing hESC-derived haematopoietic cells enhanced recovery from induced acute anaemia without significant cell engraftment, suggesting a paracrine-mediated effect.
Keywords: Acute Disease; Anemia, Hemolytic; Animals; Basic Helix-Loop-Helix Transcription Factors; Cell Differentiation; Cell Line; Cell Lineage; Cluster Analysis; Embryonic Stem Cells; Erythroid Cells; Flow Cytometry; Gene Expression Profiling; Hematopoietic Stem Cells; Humans; Mice; Myeloid Cells; Paracrine Communication; Proto-Oncogene Proteins; Reverse Transcriptase Polymerase Chain Reaction; rho GTP-Binding Proteins; Signal Transduction; Stem Cell Transplantation; T-Cell Acute Lymphocytic Leukemia Protein 1; Transcriptome

Mutation screening of multiple genes in Spanish patients with autosomal recessive retinitis pigmentosa by targeted resequencing. - González-del Pozo, María; Borrego, Salud; Barragán, Isabel; Pieras, Juan I; Santoyo, Javier; Matamala, Nerea; Naranjo, Belén; Dopazo, Joaquin; Antiňolo, Guillermo (PLoS One, 2011)
Retinitis Pigmentosa (RP) is a heterogeneous group of inherited retinal dystrophies characterised ultimately by the loss of photoreceptor cells. RP is the leading cause of visual loss in individuals younger than 60 years, with a prevalence of about 1 in 4000. The molecular genetic diagnosis of autosomal recessive RP (arRP) is challenging due to the large genetic and clinical heterogeneity. Traditional methods for sequencing arRP genes are often laborious and not easily available and a screening technique that enables the rapid detection of the genetic cause would be very helpful in the clinical practice. The goal of this study was to develop and apply microarray-based resequencing technology capable of detecting both known and novel mutations on a single high-throughput platform. Hence, the coding regions and exon/intron boundaries of 16 arRP genes were resequenced using microarrays in 102 Spanish patients with clinical diagnosis of arRP. All the detected variations were confirmed by direct sequencing and potential pathogenicity was assessed by functional predictions and frequency in controls. For validation purposes 4 positive controls for variants consisting of previously identified changes were hybridized on the array. As a result of the screening, we detected 44 variants, of which 15 are very likely pathogenic detected in 14 arRP families (14%). Finally, the design of this array can easily be transformed in an equivalent diagnostic system based on targeted enrichment followed by next generation sequencing.
Keywords: Alleles; DNA Mutational Analysis; Exons; Genetic Variation; Genome; Hispanic or Latino; Humans; Introns; Language; mutation; Mutation, Missense; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Reproducibility of Results; Retinitis pigmentosa; United States

DNA methylation epigenotypes in breast cancer molecular subtypes. - Bediaga, Naiara G; Acha-Sagredo, Amelia; Guerra, Isabel; Viguri, Amparo; Albaina, Carmen; Ruiz Diaz, Irune; Rezola, Ricardo; Alberdi, Maria Jesus; Dopazo, Joaquin; Montaner, David; Renobales, Mertxe; Fernandez, Agustin F; et al. (Breast Cancer Res, 2010)
INTRODUCTION: Identification of gene expression based breast cancer subtypes is considered as a critical means of prognostication. Genetic mutations along with epigenetic alterations contribute to gene expression changes occurring in breast cancer. So far, these epigenetic contributions to sporadic breast cancer subtypes have not been well characterized, and there is only a limited understanding of the epigenetic mechanisms affected in those particular breast cancer subtypes. The present study was undertaken to dissect the breast cancer methylome and deliver specific epigenotypes associated with particular breast cancer subtypes. METHODS: Using a microarray approach we analyzed DNA methylation in regulatory regions of 806 cancer related genes in 28 breast cancer paired samples. We subsequently performed substantial technical and biological validation by Pyrosequencing, investigating the top qualifying 19 CpG regions in independent cohorts encompassing 47 basal-like, 44 ERBB2+ overexpressing, 48 luminal A and 48 luminal B paired breast cancer/adjacent tissues. Using all-subset selection method, we identified the most subtype predictive methylation profiles in multivariable logistic regression analysis. RESULTS: The approach efficiently recognized 15 individual CpG loci differentially methylated in breast cancer tumor subtypes. We further identify novel subtype specific epigenotypes which clearly demonstrate the differences in the methylation profiles of basal-like and human epidermal growth factor 2 (HER2)-overexpressing tumors. CONCLUSIONS: Our results provide evidence that well defined DNA methylation profiles enables breast cancer subtype prediction and support the utilization of this biomarker for prognostication and therapeutic stratification of patients with breast cancer.
Keywords: Aged; Breast Neoplasms; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Profiling; Genes, p53; Genotype; Humans; Ki-67 Antigen; Middle Aged; mutation; Neoplasm Grading; Oligonucleotide Array Sequence Analysis; Receptor, ErbB-2; Tumor Suppressor Protein p53

Exploring the link between germline and somatic genetic alterations in breast carcinogenesis. - Bonifaci, Núria; Górski, Bohdan; Masojć, Bartlomiej; Wokołorczyk, Dominika; Jakubowska, Anna; Dębniak, Tadeusz; Berenguer, Antoni; Serra Musach, Jordi; Brunet, Joan; Dopazo, Joaquin; Narod, Steven A; Lubiński, Jan; et al. (PLoS One, 2010)
Recent genome-wide association studies (GWASs) have identified candidate genes contributing to cancer risk through low-penetrance mutations. Many of these genes were unexpected and, intriguingly, included well-known players in carcinogenesis at the somatic level. To assess the hypothesis of a germline-somatic link in carcinogenesis, we evaluated the distribution of somatic gene labels within the ordered results of a breast cancer risk GWAS. This analysis suggested frequent influence on risk of genetic variation in loci encoding for "driver kinases" (i.e., kinases encoded by genes that showed higher somatic mutation rates than expected by chance and, therefore, whose deregulation may contribute to cancer development and/or progression). Assessment of these predictions using a population-based case-control study in Poland replicated the association for rs3732568 in EPHB1 (odds ratio (OR) = 0.79; 95% confidence interval (CI): 0.63-0.98; P(trend) = 0.031). Analyses by early age at diagnosis and by estrogen receptor α (ERα) tumor status indicated potential associations for rs6852678 in CDKL2 (OR = 0.32, 95% CI: 0.10-1.00; P(recessive) = 0.044) and rs10878640 in DYRK2 (OR = 2.39, 95% CI: 1.32-4.30; P(dominant) = 0.003), and for rs12765929, rs9836340, rs4707795 in BMPR1A, EPHA3 and EPHA7, respectively (ERα tumor status P(interaction)<0.05). The identification of three novel candidates as EPH receptor genes might indicate a link between perturbed compartmentalization of early neoplastic lesions and breast cancer risk and progression. Together, these data may lay the foundations for replication in additional populations and could potentially increase our knowledge of the underlying molecular mechanisms of breast carcinogenesis.
Keywords: Adult; Bone Morphogenetic Protein Receptors, Type I; Breast; Breast Neoplasms; Calcium-Calmodulin-Dependent Protein Kinases; Case-Control Studies; Cyclin-Dependent Kinases; Disease Progression; Estrogen Receptor alpha; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Germ-Line Mutation; Humans; Odds Ratio; Poland; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Protein-Tyrosine Kinases; Receptor Protein-Tyrosine Kinases; Receptor, EphA3; Receptor, EphA7; Receptor, EphB1; Risk Factors

Functional genomics of 5- to 8-cell stage human embryos by blastomere single-cell cDNA analysis. - Galan, Amparo; Montaner, David; Póo, M Eugenia; Valbuena, Diana; Ruiz, Veronica; Aguilar, Cristóbal; Dopazo, Joaquin; Simon, Carlos (PLoS One, 2010)
Blastomere fate and embryonic genome activation (EGA) during human embryonic development are unsolved areas of high scientific and clinical interest. Forty-nine blastomeres from 5- to 8-cell human embryos have been investigated following an efficient single-cell cDNA amplification protocol to provide a template for high-density microarray analysis. The previously described markers, characteristic of Inner Cell Mass (ICM) (n = 120), stemness (n = 190) and Trophectoderm (TE) (n = 45), were analyzed, and a housekeeping pattern of 46 genes was established. All the human blastomeres from the 5- to 8-cell stage embryo displayed a common gene expression pattern corresponding to ICM markers (e.g., DDX3, FOXD3, LEFTY1, MYC, NANOG, POU5F1), stemness (e.g., POU5F1, DNMT3B, GABRB3, SOX2, ZFP42, TERT), and TE markers (e.g., GATA6, EOMES, CDX2, LHCGR). The EGA profile was also investigated between the 5-6- and 8-cell stage embryos, and compared to the blastocyst stage. Known genes (n = 92) such as depleted maternal transcripts (e.g., CCNA1, CCNB1, DPPA2) and embryo-specific activation (e.g., POU5F1, CDH1, DPPA4), as well as novel genes, were confirmed. In summary, the global single-cell cDNA amplification microarray analysis of the 5- to 8-cell stage human embryos reveals that blastomere fate is not committed to ICM or TE. Finally, new EGA features in human embryogenesis are presented.
Keywords: Blastomeres; DNA, Complementary; Gene Expression Profiling; Genomics; Humans; Oligonucleotide Array Sequence Analysis

Hypoxia promotes efficient differentiation of human embryonic stem cells to functional endothelium. - Prado-Lopez, Sonia; Conesa, Ana; Armiñán, Ana; Martínez-Losa, Magdalena; Escobedo-Lucea, Carmen; Gandia, Carolina; Tarazona, Sonia; Melguizo, Dario; Blesa, David; Montaner, David; Sanz-González, Silvia; Sepúlveda, Pilar; et al. (Stem Cells, 2010)
Early development of mammalian embryos occurs in an environment of relative hypoxia. Nevertheless, human embryonic stem cells (hESC), which are derived from the inner cell mass of blastocyst, are routinely cultured under the same atmospheric conditions (21% O(2)) as somatic cells. We hypothesized that O(2) levels modulate gene expression and differentiation potential of hESC, and thus, we performed gene profiling of hESC maintained under normoxic or hypoxic (1% or 5% O(2)) conditions. Our analysis revealed that hypoxia downregulates expression of pluripotency markers in hESC but increases significantly the expression of genes associated with angio- and vasculogenesis including vascular endothelial growth factor and angiopoitein-like proteins. Consequently, we were able to efficiently differentiate hESC to functional endothelial cells (EC) by varying O(2) levels; after 24 hours at 5% O(2), more than 50% of cells were CD34+. Transplantation of resulting endothelial-like cells improved both systolic function and fractional shortening in a rodent model of myocardial infarction. Moreover, analysis of the infarcted zone revealed that transplanted EC reduced the area of fibrous scar tissue by 50%. Thus, use of hypoxic conditions to specify the endothelial lineage suggests a novel strategy for cellular therapies aimed at repair of damaged vasculature in pathologies such as cerebral ischemia and myocardial infarction.
Keywords: Angiopoietin-1; Animals; biomarkers; Cell Culture Techniques; Cell Differentiation; Cell Hypoxia; Cell Transplantation; Cells, Cultured; Down-Regulation; Embryonic Stem Cells; Endothelial Cells; Gene Expression Profiling; Gene Expression Regulation; Humans; Male; Myocardial Infarction; Neovascularization, Physiologic; Oxygen; Pluripotent Stem Cells; Rats; Rats, Nude; Vascular Endothelial Growth Factor A

Multidimensional gene set analysis of genomic data. - Montaner, David; Dopazo, Joaquin (PLoS One, 2010)
Understanding the functional implications of changes in gene expression, mutations, etc., is the aim of most genomic experiments. To achieve this, several functional profiling methods have been proposed. Such methods study the behaviour of different gene modules (e.g. gene ontology terms) in response to one particular variable (e.g. differential gene expression). In spite to the wealth of information provided by functional profiling methods, a common limitation to all of them is their inherent unidimensional nature. In order to overcome this restriction we present a multidimensional logistic model that allows studying the relationship of gene modules with different genome-scale measurements (e.g. differential expression, genotyping association, methylation, copy number alterations, heterozygosity, etc.) simultaneously. Moreover, the relationship of such functional modules with the interactions among the variables can also be studied, which produces novel results impossible to be derived from the conventional unidimensional functional profiling methods. We report sound results of gene sets associations that remained undetected by the conventional one-dimensional gene set analysis in several examples. Our findings demonstrate the potential of the proposed approach for the discovery of new cell functionalities with complex dependences on more than one variable.
Keywords: Databases, Genetic; Gene Expression Profiling; Gene Regulatory Networks; Genome, Human; Genomics; Humans; Models, Statistical

Mutation spectrum of EYS in Spanish patients with autosomal recessive retinitis pigmentosa. - Barragán, Isabel; Borrego, Salud; Pieras, Juan Ignacio; González-del Pozo, María; Santoyo, Javier; Ayuso, Carmen; Baiget, Montserrat; Millán, José M; Mena, Marcela; Abd El-Aziz, Mai M; Audo, Isabelle; Zeitz, Christina; et al. (Hum Mutat, 2010)
Retinitis pigmentosa (RP) is a heterogeneous group of inherited retinal dystrophies characterised ultimately by the loss of photoreceptor cells. We have recently identified a new gene(EYS) encoding an ortholog of Drosophila space maker (spam) as a commonly mutated gene in autosomal recessive RP. In the present study, we report the identification of 73 sequence variations in EYS, of which 28 are novel. Of these, 42.9% (12/28) are very likely pathogenic, 17.9% (5/28)are possibly pathogenic, whereas 39.3% (11/28) are SNPs. In addition, we have detected 3 pathogenic changes previously reported in other populations. We are also presenting the characterisation of EYS homologues in different species, and a detailed analysis of the EYS domains, with the identification of an interesting novel feature: a putative coiled-coil domain.Majority of the mutations in the arRP patients have been found within the domain structures of EYS. The minimum observed prevalence of distinct EYS mutations in our group of patients is of 15.9% (15/94), confirming a major involvement of EYS in the pathogenesis of arRP in the Spanish population. Along with the detection of three recurrent mutations in Caucasian population, our hypothesis of EYS being the first prevalent gene in arRP has been reinforced in the present study.
Keywords: Amino Acid Sequence; Animals; Case-Control Studies; DNA Mutational Analysis; Drosophila Proteins; Evolution, Molecular; Eye Proteins; Female; Genes, Recessive; Genetic Variation; Humans; Male; Molecular Sequence Data; mutation; Pedigree; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Retinitis pigmentosa; Spain; Structural Homology, Protein

Functional signatures identified in B-cell non-Hodgkin lymphoma profiles. - Aggarwal, Mohit; Sánchez-Beato, Margarita; Gómez-López, Gonzalo; Al-Shahrour, Fátima; Martínez, Nerea; Rodríguez, Antonia; Ruiz-Ballesteros, Elena; Camacho, Francisca I; Pérez-Rosado, Alberto; de la Cueva, Paloma; Artiga, María J; Pisano, David G; et al. (Leuk Lymphoma, 2009)
Gene-expression profiling in B-cell lymphomas has provided crucial data on specific lymphoma types, which can contribute to the identification of essential lymphoma survival genes and pathways. In this study, the gene-expression profiling data of all major B-cell lymphoma types were analyzed by unsupervised clustering. The transcriptome classification so obtained, was explored using gene set enrichment analysis generating a heatmap for B-cell lymphoma that identifies common lymphoma survival mechanisms and potential therapeutic targets, recognizing sets of coregulated genes and functional pathways expressed in different lymphoma types. Some of the most relevant signatures (stroma, cell cycle, B-cell receptor (BCR)) are shared by multiple lymphoma types or subclasses. A specific attention was paid to the analysis of BCR and coregulated pathways, defining molecular heterogeneity within multiple B-cell lymphoma types.
Keywords: Adult; Cluster Analysis; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Genetic Heterogeneity; Humans; Lymphoma, B-Cell; Neoplasm Proteins; Oligonucleotide Array Sequence Analysis; RNA, Messenger; RNA, Neoplasm; Transcription, Genetic

Gene set internal coherence in the context of functional profiling. - Montaner, David; Minguez, Pablo; Al-Shahrour, Fátima; Dopazo, Joaquin (BMC Genomics, 2009)
BACKGROUND: Functional profiling methods have been extensively used in the context of high-throughput experiments and, in particular, in microarray data analysis. Such methods use available biological information to define different types of functional gene modules (e.g. gene ontology -GO-, KEGG pathways, etc.) whose representation in a pre-defined list of genes is further studied. In the most popular type of microarray experimental designs (e.g. up- or down-regulated genes, clusters of co-expressing genes, etc.) or in other genomic experiments (e.g. Chip-on-chip, epigenomics, etc.) these lists are composed by genes with a high degree of co-expression. Therefore, an implicit assumption in the application of functional profiling methods within this context is that the genes corresponding to the modules tested are effectively defining sets of co-expressing genes. Nevertheless not all the functional modules are biologically coherent entities in terms of co-expression, which will eventually hinder its detection with conventional methods of functional enrichment. RESULTS: Using a large collection of microarray data we have carried out a detailed survey of internal correlation in GO terms and KEGG pathways, providing a coherence index to be used for measuring functional module co-regulation. An unexpected low level of internal correlation was found among the modules studied. Only around 30% of the modules defined by GO terms and 57% of the modules defined by KEGG pathways display an internal correlation higher than the expected by chance.This information on the internal correlation of the genes within the functional modules can be used in the context of a logistic regression model in a simple way to improve their detection in gene expression experiments. CONCLUSION: For the first time, an exhaustive study on the internal co-expression of the most popular functional categories has been carried out. Interestingly, the real level of coexpression within many of them is lower than expected (or even inexistent), which will preclude its detection by means of most conventional functional profiling methods. If the gene-to-function correlation information is used in functional profiling methods, the results obtained improve the ones obtained by conventional enrichment methods.
Keywords: Algorithms; Breast Neoplasms; Carcinoma, Intraductal, Noninfiltrating; Computational Biology; Databases, Nucleic Acid; Female; Gene Expression Profiling; Genomics; Humans; Oligonucleotide Array Sequence Analysis; Papillomavirus Infections; Reproducibility of Results

Gene set-based analysis of polymorphisms: finding pathways or biological processes associated to traits in genome-wide association studies. - Medina, Ignacio; Montaner, David; Bonifaci, Núria; Pujana, Miguel Angel; Carbonell, José; Tárraga, Joaquín; Al-Shahrour, Fátima; Dopazo, Joaquin (Nucleic Acids Res, 2009)
Genome-wide association studies have become a popular strategy to find associations of genes to traits of interest. Despite the high-resolution available today to carry out genotyping studies, the success of its application in real studies has been limited by the testing strategy used. As an alternative to brute force solutions involving the use of very large cohorts, we propose the use of the Gene Set Analysis (GSA), a different analysis strategy based on testing the association of modules of functionally related genes. We show here how the Gene Set-based Analysis of Polymorphisms (GeSBAP), which is a simple implementation of the GSA strategy for the analysis of genome-wide association studies, provides a significant increase in the power testing for this type of studies. GeSBAP is freely available at http://bioinfo.cipf.es/gesbap/.
Keywords: Biological Phenomena; Breast Neoplasms; Female; Genes; Genetic Variation; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Software; User-Computer Interface

SNOW, a web-based tool for the statistical analysis of protein-protein interaction networks. - Minguez, Pablo; Götz, Stefan; Montaner, David; Al-Shahrour, Fátima; Dopazo, Joaquin (Nucleic Acids Res, 2009)
Understanding the structure and the dynamics of the complex intercellular network of interactions that contributes to the structure and function of a living cell is one of the main challenges of today's biology. SNOW inputs a collection of protein (or gene) identifiers and, by using the interactome as scaffold, draws the connections among them, calculates several relevant network parameters and, as a novelty among the rest of tools of its class, it estimates their statistical significance. The parameters calculated for each node are: connectivity, betweenness and clustering coefficient. It also calculates the number of components, number of bicomponents and articulation points. An interactive network viewer is also available to explore the resulting network. SNOW is available at http://snow.bioinfo.cipf.es.
Keywords: Computer Graphics; Data Interpretation, Statistical; Databases, Protein; Humans; Internet; Protein Interaction Mapping; Software

Direct functional assessment of the composite phenotype through multivariate projection strategies. - Conesa, Ana; Bro, Rasmus; Garcia-Garcia, Francisco; Prats, José Manuel; Götz, Stefan; Kjeldahl, Karin; Montaner, David; Dopazo, Joaquin (Genomics, 2008)
We present a novel approach for the analysis of transcriptomics data that integrates functional annotation of gene sets with expression values in a multivariate fashion, and directly assesses the relation of functional features to a multivariate space of response phenotypical variables. Multivariate projection methods are used to obtain new correlated variables for a set of genes that share a given function. These new functional variables are then related to the response variables of interest. The analysis of the principal directions of the multivariate regression allows for the identification of gene function features correlated with the phenotype. Two different transcriptomics studies are used to illustrate the statistical and interpretative aspects of the methodology. We demonstrate the superiority of the proposed method over equivalent approaches.
Keywords: Breast Neoplasms; Computational Biology; Databases, Genetic; Female; Gene Expression Profiling; Humans; Mathematical Computing; Multivariate Analysis; Phenotype

Expression and microarrays. - Dopazo, Joaquin; Al-Shahrour, Fátima (Methods Mol Biol, 2008)
High throughput methodologies have increased by several orders of magnitude the amount of experimental microarray data available. Nevertheless, translating these data into useful biological knowledge remains a challenge. There is a risk of perceiving these methodologies as mere factories that produce never-ending quantities of data if a proper biological interpretation is not provided. Methods of interpreting these data are continuously evolving. Typically, a simple two-step approach has been used, in which genes of interest are first selected based on thresholds for the experimental values, and then enrichment in biologically relevant terms in the annotations of these genes is analyzed in a second step. For various reasons, such methods are quite poor in terms of performance and new procedures inspired by systems biology that directly address sets of functionally related genes are currently under development.
Keywords: Animals; Computational Biology; gene expression; Gene Expression Profiling; Humans; Oligonucleotide Array Sequence Analysis

Joint annotation of coding and non-coding single nucleotide polymorphisms and mutations in the SNPeffect and PupaSuite databases. - Reumers, Joke; Conde, Lucia; Medina, Ignacio; Maurer-Stroh, Sebastian; Van Durme, Joost; Dopazo, Joaquin; Rousseau, Frederic; Schymkowitz, Joost (Nucleic Acids Res, 2008)
Single nucleotide polymorphisms (SNPs) are, together with copy number variation, the primary source of variation in the human genome. SNPs are associated with altered response to drug treatment, susceptibility to disease and other phenotypic variation. Furthermore, during genetic screens for disease-associated mutations in groups of patients and control individuals, the distinction between disease causing mutation and polymorphism is often unclear. Annotation of the functional and structural implications of single nucleotide changes thus provides valuable information to interpret and guide experiments. The SNPeffect and PupaSuite databases are now synchronized to deliver annotations for both non-coding and coding SNP, as well as annotations for the SwissProt set of human disease mutations. In addition, SNPeffect now contains predictions of Tango2: an improved aggregation detector, and Waltz: a novel predictor of amyloid-forming sequences, as well as improved predictors for regions that are recognized by the Hsp70 family of chaperones. The new PupaSuite version incorporates predictions for SNPs in silencers and miRNAs including their targets, as well as additional methods for predicting SNPs in TFBSs and splice sites. Also predictions for mouse and rat genomes have been added. In addition, a PupaSuite web service has been developed to enable data access, programmatically. The combined database holds annotations for 4,965,073 regulatory as well as 133,505 coding human SNPs and 14,935 disease mutations, and phenotypic descriptions of 43,797 human proteins and is accessible via http://snpeffect.vib.be and http://pupasuite.bioinfo.cipf.es/.
Keywords: Amino Acid Substitution; Animals; Databases, Genetic; Genetic Diseases, Inborn; HSP70 Heat-Shock Proteins; Humans; Internet; Mice; MicroRNAs; mutation; Polymorphism, Single Nucleotide; Proteins; Rats; RNA Splice Sites; Transcription Factors

PhylomeDB: a database for genome-wide collections of gene phylogenies. - Huerta-Cepas, Jaime; Bueno, Anibal; Dopazo, Joaquin; Gabaldón, Toni (Nucleic Acids Res, 2008)
The complete collection of evolutionary histories of all genes in a genome, also known as phylome, constitutes a valuable source of information. The reconstruction of phylomes has been previously prevented by large demands of time and computer power, but is now feasible thanks to recent developments in computers and algorithms. To provide a publicly available repository of complete phylomes that allows researchers to access and store large-scale phylogenomic analyses, we have developed PhylomeDB. PhylomeDB is a database of complete phylomes derived for different genomes within a specific taxonomic range. All phylomes in the database are built using a high-quality phylogenetic pipeline that includes evolutionary model testing and alignment trimming phases. For each genome, PhylomeDB provides the alignments, phylogentic trees and tree-based orthology predictions for every single encoded protein. The current version of PhylomeDB includes the phylomes of Human, the yeast Saccharomyces cerevisiae and the bacterium Escherichia coli, comprising a total of 32 289 seed sequences with their corresponding alignments and 172 324 phylogenetic trees. PhylomeDB can be publicly accessed at http://phylomedb.bioinfo.cipf.es.
Keywords: Base Sequence; Escherichia coli; Genes; Genomics; History, Ancient; Humans; Phylogeny; Proteins; Saccharomyces cerevisiae; Sequence Alignment

Use of estimated evolutionary strength at the codon level improves the prediction of disease-related protein mutations in humans. - Capriotti, Emidio; Arbiza, Leonardo; Casadio, Rita; Dopazo, Joaquin; Dopazo, Hernán; Marti-Renom, Marc A (Hum Mutat, 2008)
Predicting the functional impact of protein variation is one of the most challenging problems in bioinformatics. A rapidly growing number of genome-scale studies provide large amounts of experimental data, allowing the application of rigorous statistical approaches for predicting whether a given single point mutation has an impact on human health. Up until now, existing methods have limited their source data to either protein or gene information. Novel in this work, we take advantage of both and focus on protein evolutionary information by using estimated selective pressures at the codon level. Here we introduce a new method (SeqProfCod) to predict the likelihood that a given protein variant is associated with human disease or not. Our method relies on a support vector machine (SVM) classifier trained using three sources of information: protein sequence, multiple protein sequence alignments, and the estimation of selective pressure at the codon level. SeqProfCod has been benchmarked with a large dataset of 8,987 single point mutations from 1,434 human proteins from SWISS-PROT. It achieves 82% overall accuracy and a correlation coefficient of 0.59, indicating that the estimation of the selective pressure helps in predicting the functional impact of single-point mutations. Moreover, this study demonstrates the synergic effect of combining two sources of information for predicting the functional effects of protein variants: protein sequence/profile-based information and the evolutionary estimation of the selective pressures at the codon level. The results of large-scale application of SeqProfCod over all annotated point mutations in SWISS-PROT (available for download at http://sgu.bioinfo.cipf.es/services/Omidios/; last accessed: 24 August 2007), could be used to support clinical studies.
Keywords: Algorithms; Codon; Computational Biology; Databases, Protein; DNA Mutational Analysis; Evolution, Molecular; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; Iduronic Acid; Point Mutation; Polymorphism, Single Nucleotide; Proteins; Tumor Suppressor Protein p53

Evidence for systems-level molecular mechanisms of tumorigenesis. - Hernández, Pilar; Huerta-Cepas, Jaime; Montaner, David; Al-Shahrour, Fátima; Valls, Joan; Gómez, Laia; Capellà, Gabriel; Dopazo, Joaquin; Pujana, Miguel Angel (BMC Genomics, 2007)
BACKGROUND: Cancer arises from the consecutive acquisition of genetic alterations. Increasing evidence suggests that as a consequence of these alterations, molecular interactions are reprogrammed in the context of highly connected and regulated cellular networks. Coordinated reprogramming would allow the cell to acquire the capabilities for malignant growth. RESULTS: Here, we determine the coordinated function of cancer gene products (i.e., proteins encoded by differentially expressed genes in tumors relative to healthy tissue counterparts, hereafter referred to as "CGPs") defined as their topological properties and organization in the interactome network. We show that CGPs are central to information exchange and propagation and that they are specifically organized to promote tumorigenesis. Centrality is identified by both local (degree) and global (betweenness and closeness) measures, and systematically appears in down-regulated CGPs. Up-regulated CGPs do not consistently exhibit centrality, but both types of cancer products determine the overall integrity of the network structure. In addition to centrality, down-regulated CGPs show topological association that correlates with common biological processes and pathways involved in tumorigenesis. CONCLUSION: Given the current limited coverage of the human interactome, this study proposes that tumorigenesis takes place in a specific and organized way at the molecular systems-level and suggests a model that comprises the precise down-regulation of groups of topologically-associated proteins involved in particular functions, orchestrated with the up-regulation of specific proteins.
Keywords: Cell Transformation, Neoplastic; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Male; Models, Biological; Models, Genetic; Models, Statistical; Neoplasm Proteins; Neoplasms; Prostatic Neoplasms; Protein Interaction Mapping; RNA, Messenger; Signal Transduction; Systems biology

FatiGO +: a functional profiling tool for genomic data. Integration of functional annotation, regulatory motifs and interaction data with microarray experiments. - Al-Shahrour, Fátima; Minguez, Pablo; Tárraga, Joaquín; Medina, Ignacio; Alloza, Eva; Montaner, David; Dopazo, Joaquin (Nucleic Acids Res, 2007)
The ultimate goal of any genome-scale experiment is to provide a functional interpretation of the data, relating the available information with the hypotheses that originated the experiment. Thus, functional profiling methods have become essential in diverse scenarios such as microarray experiments, proteomics, etc. We present the FatiGO+, a web-based tool for the functional profiling of genome-scale experiments, specially oriented to the interpretation of microarray experiments. In addition to different functional annotations (gene ontology, KEGG pathways, Interpro motifs, Swissprot keywords and text-mining based bioentities related to diseases and chemical compounds) FatiGO+ includes, as a novelty, regulatory and structural information. The regulatory information used includes predictions of targets for distinct regulatory elements (obtained from the Transfac and CisRed databases). Additionally FatiGO+ uses predictions of target motifs of miRNA to infer which of these can be activated or deactivated in the sample of genes studied. Finally, properties of gene products related to their relative location and connections in the interactome have also been used. Also, enrichment of any of these functional terms can be directly analysed on chromosomal coordinates. FatiGO+ can be found at: http://www.fatigoplus.org and within the Babelomics environment http://www.babelomics.org.
Keywords: Amino Acid Motifs; Animals; Binding Sites; Computational Biology; Gene Expression Profiling; Genes; Genomics; Humans; Internet; Oligonucleotide Array Sequence Analysis; Programming Languages; Software; Systems Integration; Transcription Factors

ISACGH: a web-based environment for the analysis of Array CGH and gene expression which includes functional profiling. - Conde, Lucia; Montaner, David; Burguet-Castell, Jordi; Tárraga, Joaquín; Medina, Ignacio; Al-Shahrour, Fátima; Dopazo, Joaquin (Nucleic Acids Res, 2007)
We present the ISACGH, a web-based system that allows for the combination of genomic data with gene expression values and provides different options for functional profiling of the regions found. Several visualization options offer a convenient representation of the results. Different efficient methods for accurate estimation of genomic copy number from array-CGH hybridization data have been included in the program. Moreover, the connection to the gene expression analysis package GEPAS allows the use of different facilities for data pre-processing and analysis. A DAS server allows exporting the results to the Ensembl viewer where contextual genomic information can be obtained. The program is freely available at: http://isacgh.bioinfo.cipf.es or within http://www.gepas.org.
Keywords: Animals; Cluster Analysis; Computational Biology; Computer Graphics; Gene Expression Profiling; Humans; Internet; Models, Genetic; Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; Programming Languages; Software; Systems Integration; User-Computer Interface